Free-cutting copper alloy and method for producing free-cutting copper alloy

By modifying the β phase into the β1 phase in the Cu-Zn-Si alloy and rapidly cooling treatment, the shortcomings in existing easy-to-cut copper alloys in terms of corrosion resistance and Pb content are solved, and efficient cutting performance and environmental protection performance are improved.

CN120153107APending Publication Date: 2025-06-13MITSUBISHI MATERIALS CORP
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202480004633.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-05
Filing Date
2024-04-25
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

The existing easy-to-cut copper alloys have shortcomings in their dezincification resistance and stress corrosion resistance, and contain high Pb, which is difficult to meet environmental protection and performance requirements.

Method used

By modifying the β phase into the β1 phase in the Cu-Zn-Si alloy, Si and P are solidly dissolved in the β phase at high temperature, and forming the β1 phase through rapid cooling treatment, reducing the Pb content and improving the machinability, corrosion resistance and strength of the alloy.

Benefits of technology

The alloy has excellent machinability, dezincification resistance, stress corrosion resistance, and crack resistance. The balance between strength and ductility is good, and the Pb content is greatly reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005380175970000201
    Figure BDA0005380175970000201
  • Figure BDA0005380175970000211
    Figure BDA0005380175970000211
  • Figure BDA0005380175970000221
    Figure BDA0005380175970000221
Patent Text Reader

Abstract

This free-cutting copper alloy contains specific amounts of Cu, Si, Pb, and P, and contains a specific amount of Bi as an optional element, with the remainder being Zn and unavoidable impurities in which the total content of Fe, Mn, Co, and Cr is less than a specific amount and the content of Al is less than a specific amount. The composition relationships f1, f2, and f0 defined by the composition of each element, the structure relationships f3, f4, and f5 defined by the area ratio of the constituent phases of the metallographic structure, and the structure and composition relationship f6 defined by the composition and the metallographic structure are each within a specific range, and the grain boundary of the modified beta1 phase can be observed when the modified beta1 phase is etched with a mixed solution of hydrogen peroxide and ammonia water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a free-cutting copper alloy and a method for manufacturing the same, and the free-cutting copper alloy has good corrosion resistance (especially dezincification corrosion resistance), stress corrosion cracking resistance, high strength, and a significantly reduced Pb content.

[0002] The present invention relates to a free-cutting copper alloy used in parts that require cutting and a method for manufacturing the free-cutting copper alloy. The parts that require cutting are appliances and parts for drinking water that humans and animals ingest daily, appliances and parts for sanitary equipment such as kitchens, bathrooms, and toilets, water meters, musical instruments, tableware, drainage appliances and parts, industrial pipe parts, electrical and electronic equipment parts, automotive parts, mechanical parts, stationery, toys, sliding parts, measuring instrument parts, precision mechanical parts, medical parts, and parts related to liquids or gases such as hydrogen. As specific part names, faucets, mixer faucets, faucet fittings, stop faucets, valves, joints, valves, showerheads, cocks, gears, shafts, bearings, rotating shafts (shafts), sleeves, mandrels, sensors, bolts, nuts, flared nuts, pen tips, inserted nuts, cap nuts, threaded pipes, gaskets, screws, etc. can be cited.

[0003] This application claims priority based on Japanese Patent Application No. 2023-075579 filed on May 1, 2023, and Japanese Patent Application No. 2023-173342 filed on October 5, 2023, and incorporates their contents herein. Background Art

[0004] Conventionally, in appliances and parts related to drinking water, sanitary equipment, water meters, musical instruments, tableware, electrical / home appliance / electronic equipment parts, automotive parts, mechanical parts, stationery, precision mechanical parts, medical parts, and appliances and parts related to industrial water, drainage, hydrogen, etc. (as part names, parts such as faucets, mixer faucets, stop faucets, valves, cocks, joints, gears, sensors, nuts, screws, etc. can be cited), Cu-Zn-Pb alloys (so-called free-cutting brass rods, forging brass, casting brass) or Cu-Sn-Zn-Pb alloys (so-called bronze castings: gunmetal) are generally used. Among them, the Cu-Zn-Pb alloy has excellent machinability, antibacterial properties, and good corrosion resistance, contains 56 to 65% by mass of Cu, 1 to 4% by mass of Pb, and the balance is Zn; the Cu-Sn-Zn-Pb alloy contains 80 to 88% by mass of Cu, 2 to 8% by mass of Sn, 1 to 8% by mass of Pb, and the balance is Zn.

[0005] However, in recent years, the impact of Pb on the human body or the environment has been a concern, and countries have actively carried out control activities regarding Pb. For example, in the state of California in the United States, since January 2010, regulations have come into effect that limit the Pb content in drinking water appliances, etc. to 0.25 mass% or less. In countries other than the United States, such control activities are also being rapidly promoted, and the development of a copper alloy material that can respond to the control of Pb content is required.

[0006] Moreover, for other industrial fields, such as the electrical and electronic equipment, automotive, and machinery industries, for example, in the Restriction of Hazardous Substances (RoHS) and End-of-life Vehicle (ELV) directives in Europe, although the Pb content of free-cutting copper alloys is exceptionally allowed up to 4 mass%, similar to the drinking water field, discussions are also actively underway to strengthen the control of Pb content, including the abolition of exceptions.

[0007] In this trend of strengthening the control of Pb in free-cutting copper alloys, it is advocated to use (1) Cu-Zn-Bi alloys and Cu-Zn-Bi-Se alloys containing Bi with cutting functions instead of Pb and, if necessary, also containing Se in addition to Bi; (2) Cu-Zn alloys containing a high concentration of Zn and increasing the β phase to improve machinability; or (3) Cu-Zn-Si alloys containing a large amount of γ phase and κ phase with excellent cutting performance instead of Pb; and (4) Cu-Zn-Si-Pb alloys that improve the machinability of the β phase by containing Si, etc., to replace Pb-containing free-cutting copper alloys containing 56 - 65 mass% Cu, 1 - 4 mass% Pb, and the balance being Zn, especially the free-cutting brass containing 3 mass% Pb that is most widely used worldwide (Japanese JIS specification: C3604; American ASTM specification: C36000; European EN specification: CW614N).

[0008] For example, in Patent Document 1, since 0.3 - 4 mass%, preferably 1.8 - 3.2 mass% of Bi is added to a Cu-Zn alloy and the β phase has poor dezincification corrosion resistance, the machinability and dezincification corrosion resistance are improved by reducing the β phase and annealing at 350 - 550 °C to break the β phase with the α phase.

[0009] However, alloys containing Bi instead of Pb have many problems, including: the cutting function of Bi is worse than that of Pb; Bi may be harmful to the environment and the human body in the same way as Pb; there are resource problems because Bi is a rare metal; Bi makes the copper alloy material brittle, etc.

[0010] Furthermore, as shown in Patent Document 1, conventional Cu-Zn alloys have poor dezincification corrosion resistance in the β phase, and measures to improve this resistance substantially require reduction of the β phase and annealing for dividing the β phase with the α phase.

[0011] In addition, Cu-Zn binary alloys containing a large amount of β phase help improve machinability, but compared with Pb, the machinability of the β phase is poor, and the dezincification corrosion resistance and stress corrosion cracking resistance are poor, so it is ultimately unable to replace the Pb-containing free-cutting copper alloy.

[0012] Therefore, as a free-cutting copper alloy, for example, Patent Documents 2 to 8 propose a Cu—Zn—Si alloy containing Si instead of Pb.

[0013] In Patent Documents 2 to 7, the amount of Cu is about 58 to 65% by mass, and the amount of Si is about 0.2 to 1.5% by mass. The presence of Si contained in the β phase and fine P compounds formed by P and Zn, etc., improves the machinability, and the area ratios of the β phase and the γ phase are specified. The presence of the P compound and the presence of a small amount of Pb complement each other to achieve excellent machinability. However, as disclosed in Patent Document 1, it is well known that the β phase of the Cu-Zn alloy has poor dezincification corrosion resistance, which leads to poor stress corrosion cracking resistance. Therefore, in Patent Documents 2 to 7, no specific data related to dezincification corrosion resistance and stress corrosion cracking resistance are disclosed, and it is speculated that the technical problems of the β phase of the Cu-Zn alloy in the past, namely, dezincification corrosion resistance and stress corrosion cracking resistance, have not been improved.

[0014] In Patent Document 8, the amount of Cu is 71.5 to 78.5 mass%, the amount of Si is 2.0 to 4.5 mass%, and the total area of ​​the γ phase and κ phase formed by the alloy with high Cu and Si concentrations, which have excellent machinability, is specified, and excellent machinability is achieved by containing a small amount of Pb of 0.02 mass% or less. In addition, by containing Sn and Al in an amount of 0.1 mass% or more, a large amount of γ phase is formed, thereby further improving machinability and corrosion resistance.

[0015] Furthermore, in Patent Document 9, a Cu-Zn-Sn alloy contains a small amount of Si, Pb, P or Fe, and contains 0.5 mass % or less of Pb, and excellent machinability is obtained by improving the manufacturing method, dispersing Pb-rich particles in the matrix, and increasing the number density of Pb-rich particles present in the α phase. Furthermore, in Patent Document 9, in order to improve the dezincification corrosion resistance, a finishing heat treatment of 400 to 600° C. is substantially required.

[0016] In Patent Document 10, a technique for near-net shaping of a hollow hot forging using a hollow billet in a Cu-Zn-Si-Pb-P alloy is involved, and a copper alloy with restricted area ratios of β-phase, γ-phase, and μ-phase is proposed.

[0017] In Patent Document 11, a copper alloy casting is proposed, which selectively contains Si, Pb, and Sn in a Cu-Zn-Zr-P alloy, and the grain is refined by the action of Zr and P.

[0018] In Patent Document 12, a copper alloy is proposed, which selectively contains Si and Pb in a Cu-Zn-Sn-Al alloy, has restricted area ratios of γ-phase and β-phase, and has excellent anti-discoloration property.

[0019] In Patent Document 13, a copper alloy casting without Pb in a Cu-Zn-Si-Sn-Al-P alloy is proposed.

[0020] In Patent Document 14, a copper alloy is proposed, in a Cu-Zn-Si-Sn-Al alloy, for improving corrosion resistance, the apparent Zn content is important, and machinability is improved by substantially containing a large amount of Pb or Bi.

[0021] In Patent Document 15, the following example is described: a copper alloy casting without Pb, which contains 65 mass% or more of Cu in a Cu-Zn-Si alloy, has good castability and mechanical strength, improves machinability through γ-phase, and contains a large amount of Sn, Al, Mn, Ni, and Sb.

[0022] Patent Document 1: Japanese Patent Laid-Open No. 2002-003967

[0023] Patent Document 2: Japanese Patent Laid-Open No. 2021-042461

[0024] Patent Document 3: Japanese Patent Laid-Open No. 2021-042459

[0025] Patent Document 4: Japanese Patent Laid-Open No. 2021-042460

[0026] Patent Document 5: International Publication No. 2020 / 261666

[0027] Patent Document 6: Japanese Patent Laid-Open No. 2021-042462

[0028] Patent Document 7: International Publication No. 2021 / 117528

[0029] Patent Document 8: International Publication No. 2007 / 034571

[0030] Patent Document 9: Japanese Patent Application Laid-Open No. 2016-194123

[0031] Patent Document 10: WO 2013 / 065830

[0032] Patent Document 11: WO 2006 / 016630

[0033] Patent Document 12: WO 2015 / 046421

[0034] Patent Document 13: Japanese Patent Application Laid-Open No. 2010-133006

[0035] Patent Document 14: Japanese Patent Application Laid-Open No. 2018-048398

[0036] Patent Document 15: Japanese Patent Application Laid-Open No. 2019-508584

[0037] As shown in these Patent Documents 1 to 15, no substantial improvement has been found in the past in relation to the major prior art problems, namely, dezincification corrosion resistance and stress corrosion cracking resistance of the β-phase present in the Cu-Zn alloy. Further, no alloy has been disclosed which, in a Cu-Zn alloy, contains Pb and Bi in amounts less than 0.2%, and which, even without the need to contain Bi, has a low cutting resistance and exhibits excellent machinability under high-speed cutting conditions where the cutting speed exceeds 100 m / minute. Summary of the Invention

[0038] The present invention has been made to solve the problems of the prior art, and an object thereof is to provide a free-cutting copper alloy and a method for producing the same, the free-cutting copper alloy having excellent hot workability and machinability, good dezincification corrosion resistance and stress corrosion cracking resistance despite containing a large amount of β-phase (β1-phase described below), high strength, good balance between strength and ductility, and a significantly reduced Pb content.

[0039] To solve the above problems and achieve the above object, the present inventors have conducted intensive studies and obtained the following findings.

[0040] In addition, in this specification, unless otherwise specified, the β phase includes the β' phase, the γ phase includes the γ' phase, and the α phase includes the α' phase. The β1 phase is a modified β phase, which is distinguished from the β phase. The β1 phase is characterized in that when hydrogen peroxide and ammonia water are used as the etching solution and observed with a metallographic microscope, a grain boundary pattern, i.e., grain boundaries, is observed within the β1 phase. Regarding the β phase existing in conventional Cu-Zn alloys, Cu-Zn-Bi alloys, Cu-Zn-Si alloys, etc., even when etched with hydrogen peroxide and ammonia water, no grain boundaries are observed within the β phase. Therefore, the β phase and the β1 phase can be clearly distinguished. Grain boundaries are sometimes simply referred to as grain boundaries. Hot-worked parts include hot-extruded parts, hot-forged parts, and hot-rolled parts. Cold workability refers to the performance of processing such as drawing, wire drawing, rolling, caulking, and bending carried out in the cold state. Unless otherwise specified, good and excellent machinability means that when machining the outer circumference with a lathe, the cutting resistance is small and the chip breakability is good or excellent. Conductivity refers to electrical conductivity, heat conductivity, and electric conductance. Cooling rate refers to the average cooling rate within a certain temperature range. One day and night refers to one day. Actual operation refers to manufacturing by actual production equipment.

[0041] In the above Patent Document 8, the β phase in the Cu-Zn-Si alloy is of little help to the machinability of the copper alloy and instead hinders the machinability of the copper alloy. In Patent Documents 10, 11, and 12, the amount of the β phase is also significantly limited. In Patent Document 1, as a method for improving the dezincification corrosion resistance of the β phase, it is necessary to reduce the β phase and perform annealing at 350 to 550 °C to break the β phase with the α phase. In Patent Document 9, in order to improve the dezincification corrosion resistance of the β phase, it is necessary to contain Sn more than Si, heat to a temperature of 700 to 850 °C, and perform hot extrusion. As finish heat treatment, it is held at 400 to 600 °C for 30 minutes or more, and heat treatment is carried out under the condition that the average cooling rate from 400 to 200 °C is 0.2 to 10 °C / second.

[0042] On the other hand, in Patent Documents 2 to 7, it is found that in the Cu-Zn-Si alloy, first, making the β phase contain a certain amount of Si has a significant effect on the machinability of the β phase itself. And by the synergistic effect of the presence of fine P compounds, containing a small amount of Pb, and optionally containing Bi, the alloy has excellent machinability. However, in order for the P compounds to exist, it is preferably required that the average cooling rate in the temperature range from about 530 °C to about 450 °C after hot working is about 0.1 °C / minute or more and about 70 °C / minute or less.

[0043] However, in Patent Documents 2 to 7, no information related to dezincification corrosion resistance and stress corrosion cracking resistance is disclosed. Also, modification of the β-phase itself is not mentioned. That is, it is speculated that the dezincification corrosion resistance and stress corrosion cracking resistance of the β-phase present in the Cu-Zn-Si alloy have not been improved, and the machinability has not been further improved.

[0044] The present inventors have also been committed to the modification of the β-phase itself in the Cu-Zn-Si alloy. As a result of in-depth research, it has been found that even in the absence of P compounds, by modifying the β-phase, i.e., the β1-phase, it is possible to further improve the machinability, especially the machinability during high-speed cutting, without necessarily containing Bi, and it is possible to significantly improve the long-term problems of the Cu-Zn-based alloy, namely, the dezincification corrosion resistance and stress corrosion cracking resistance of the β-phase. In addition, an alloy containing the β1-phase instead of the β-phase can further increase the strength without impairing the ductility. The β1-phase is obtained by the following method: First, a certain amount of Si and P need to be dissolved in the β-phase, and then, while maintaining the β-phase state at 500 to 670 °C, the cooling rate when cooling to room temperature is increased, thereby restoring the state of the metallographic structure at high temperature to room temperature.

[0045] However, the β1-phase is easily distinguishable from the β-phase of the Cu-Zn-based alloy. The surface is mirror-polished (mirror-ground), and etched with a mixed solution of hydrogen peroxide and ammonia water. An aqueous solution obtained by mixing 3 mL of 3 vol% hydrogen peroxide water and 22 mL of 14 vol% ammonia water is used for etching. The ground surface of the metal is immersed in this aqueous solution at room temperature of about 15 to about 25 °C for about 2 to about 10 seconds. When observed with a metallurgical microscope at 200 to 1000 times magnification, grain boundaries, i.e., crystal grain boundaries, can be seen in the β1-phase, while no grain boundaries are observed in the β-phase of the ordinary Cu-Zn-based alloy. Regarding this etching solution, its use is also disclosed in Patent Documents 2 to 7, 10, and 11, and the metallographic structure is described.

[0046] In order to maintain the conditions for obtaining the β1 phase, that is, the state of the β phase at 500 to 670 °C after hot working and restore it to room temperature, during the cooling process after hot working, the hot-worked piece needs to be cooled at a temperature lower than 670 °C and higher than 500 °C. During the cooling process, the cooling is carried out in such a way that the average cooling rate in the temperature range from the cooling start temperature to 500 °C exceeds 300 °C / minute, and then the cooling is carried out in such a way that the average cooling rate in the temperature range from 500 °C to 300 °C is at least more than 300 °C / minute. In this specification, unless otherwise specified, the cooling process refers to an operation of controlling the cooling rate by water cooling or a method similar thereto rather than natural cooling. In Patent Documents 2 to 7, in order to obtain a compound containing fine P, the hot-worked piece needs to be cooled in such a way that the average cooling rate in the temperature range of about 530 °C to about 450 °C after hot working is about 0.1 °C / minute or more and about 70 °C / minute or less. That is, obviously, this application is in the opposite direction (gives opposite teachings) to Patent Documents 2 to 7.

[0047] However, for example, when the cooling rate near 520 °C after hot working is 60 °C / minute and the average cooling rate in the temperature range from the cooling start temperature of 520 °C to 500 °C exceeds 300 °C / minute, in this application, there are sometimes alloys containing both the β1 phase and the P compound.

[0048] With the β1 phase in this application, even without the P compound disclosed in Patent Documents 2 to 7, the machinability of the Cu-Zn-Si alloy, especially rapid machining, is greatly improved. Moreover, through the synergistic effect of the β1 phase and fine Pb particles or particles containing Pb and Bi, the reduction of cutting resistance and the breaking of chips are promoted.

[0049] More importantly, the dezincification corrosion resistance and stress corrosion cracking resistance, which are the main unsolved problems of the previous β phase, are greatly improved and solved by modifying the β phase to the β1 phase. Moreover, the mechanical properties inherit the high strength of the previous β phase, and the ductility is improved, having higher strength and a better balance between strength and ductility. Based on the above, a copper alloy is invented, which has machinability equivalent to that of the previous free-cutting brass, and has good dezincification corrosion resistance and stress corrosion cracking resistance and higher strength compared with the previous free-cutting brass.

[0050] The free-cutting copper alloy of aspect 1 of the present invention is characterized in that it contains more than 60.5% by mass and less than 65.0% by mass of Cu, more than 0.50% by mass and less than 1.20% by mass of Si, 0.002% by mass or more and less than 0.20% by mass of Pb, and more than 0.01% by mass and less than 0.18% by mass of P, and contains 0.0001% by mass or more and less than 0.20% by mass of Bi as an optional element. The balance is composed of Zn and inevitable impurities. In the inevitable impurities, the total content of Fe, Mn, Co, and Cr is less than 0.40% by mass, and the content of Al is less than 0.30% by mass. When the content of Cu is set as [Cu]% by mass, the content of Si is set as [Si]% by mass, the content of Pb is set as [Pb]% by mass, the content of P is set as [P]% by mass, and the content of Bi is set as [Bi]% by mass, the following relationships hold: 57.5 ≤ f1 = [Cu] - 4.6×[Si] + 0.5×([Pb] + [Bi]) - [P] ≤ 60.5. When Bi is included, the following relationship further holds: 0.003 ≤ f2 = [Pb] + [Bi] < 0.20. And when, in the constituent phases of the metallographic structure other than non-metallic inclusions, the area ratio of the α-phase is set as α%, the area ratio of the γ-phase is set as γ%, and the area ratio of the β1-phase, which is a modified β-phase, is set as β1%, the following relationships hold: 20 ≤ f3 = α < 75, 25 < f4 = β1 ≤ 80, 0 ≤ f5 = γ < 4, 27 < f6 = β1×([Si]) 1 / 2 -γ×2 + ([Pb] + [Bi]) 1 / 2 ×20 + ([P]) 1 / 2 ×15. Regarding the β1-phase, when etched with a mixed solution of hydrogen peroxide and ammonia water, grain boundaries can be observed.

[0051] The free-cutting copper alloy of aspect 2 of the present invention is characterized in that it contains Cu in an amount of 61.2% by mass or more and 64.8% by mass or less, Si in an amount of 0.65% by mass or more and 1.10% by mass or less, Pb in an amount of 0.003% by mass or more and less than 0.10% by mass, and P in an amount of 0.03% by mass or more and 0.15% by mass or less, and contains Bi in an amount of 0.001% by mass or more and less than 0.10% by mass as an optional element, and the balance is composed of Zn and inevitable impurities. In the inevitable impurities, the total content of Fe, Mn, Co, and Cr is less than 0.30% by mass, and the content of Al is less than 0.15% by mass. When the content of Cu is set as [Cu]% by mass, the content of Si is set as [Si]% by mass, the content of Pb is set as [Pb]% by mass, the content of P is set as [P]% by mass, and the content of Bi is set as [Bi]% by mass, the following relationships hold: 58.0 ≤ f1 = [Cu] - 4.6×[Si] + 0.5×([Pb] + [Bi]) - [P] ≤ 60.2. When Bi is contained, the following relationship further holds: 0.004 ≤ f2 = [Pb] + [Bi] < 0.10. And when, in the constituent phases of the metallographic structure other than non-metallic inclusions, the area ratio of the α-phase is set as α%, the area ratio of the γ-phase is set as γ%, and the area ratio of the β1-phase, which is a modified β-phase, is set as β1%, the following relationships hold: 30 ≤ f3 = α ≤ 70, 30 ≤ f4 = β1 ≤ 70, 0 ≤ f5 = γ < 1, 35 < f6 = β1×([Si]) 1 / 2 -γ×2 + ([Pb] + [Bi]) 1 / 2 ×20 + ([P]) 1 / 2 ×15. Regarding the β1-phase, when etched with a mixed solution of hydrogen peroxide and ammonia water, grain boundaries can be observed.

[0052] The free-cutting copper alloy according to aspect 3 of the present invention is characterized in that it contains more than 60.5% by mass and less than 65.0% by mass of Cu, more than 0.50% by mass and less than 1.20% by mass of Si, 0.002% by mass or more and less than 0.20% by mass of Pb, more than 0.01% by mass and less than 0.18% by mass of P, and more than 0.05% by mass and less than 0.90% by mass of Sn, and contains 0.0001% by mass or more and less than 0.20% by mass of Bi as an optional element, and the balance is composed of Zn and inevitable impurities. In the inevitable impurities, the total content of Fe, Mn, Co and Cr is less than 0.40% by mass, and the content of Al is less than 0.30% by mass. When the content of Cu is set as [Cu]% by mass, the content of Si is set as [Si]% by mass, the content of Pb is set as [Pb]% by mass, the content of P is set as [P]% by mass, the content of Bi is set as [Bi]% by mass, and the content of Sn is set as [Sn]% by mass, it has the following relationship: 57.5 ≤ f1 = [Cu] - 4.6×[Si] + 0.5×([Pb] + [Bi]) - [P] - [Sn] ≤ 60.5, and further has the following relationship: f0 = [Sn] / [Si] < 1. When Bi is contained, it has the following relationship: 0.003 ≤ f2 = [Pb] + [Bi] < 0.20, and when, in the constituent phases of the metallographic structure other than non-metallic inclusions, the area ratio of the α-phase is set as α%, the area ratio of the γ-phase is set as γ%, and the area ratio of the β1-phase, which is a modified β-phase, is set as β1%, it has the following relationships: 20 ≤ f3 = α < 75, 25 < f4 = β1 ≤ 80, 0 ≤ f5 = γ < 4, 27 < f6 = β1×([Si]) 1 / 2 -γ×2 + ([Pb] + [Bi]) 1 / 2 ×20 + ([P]) 1 / 2 ×15. Regarding the β1-phase, when etched with a mixed solution of hydrogen peroxide and ammonia water, grain boundaries can be observed.

[0053] The free-cutting copper alloy of aspect 4 of the present invention is characterized in that it contains Cu in an amount of 61.2% by mass or more and 64.8% by mass or less, Si in an amount of 0.65% by mass or more and 1.10% by mass or less, Pb in an amount of 0.003% by mass or more and less than 0.10% by mass, P in an amount of 0.03% by mass or more and 0.15% by mass or less, and Sn in an amount of 0.10% by mass or more and less than 0.50% by mass, and contains Bi in an amount of 0.001% by mass or more and less than 0.10% by mass as an optional element. The balance is composed of Zn and inevitable impurities. In the inevitable impurities, the total content of Fe, Mn, Co, and Cr is less than 0.30% by mass, and the content of Al is less than 0.15% by mass. When the content of Cu is set as [Cu]% by mass, the content of Si is set as [Si]% by mass, the content of Pb is set as [Pb]% by mass, the content of P is set as [P]% by mass, the content of Bi is set as [Bi]% by mass, and the content of Sn is set as [Sn]% by mass, the following relationships hold: 58.0 ≤ f1 = [Cu] - 4.6 × [Si] + 0.5 × ([Pb] + [Bi]) - [P] - [Sn] ≤ 60.2, and further the following relationship holds: f0 = [Sn] / [Si] < 0.6. When Bi is contained, the following relationship holds: 0.004 ≤ f2 = [Pb] + [Bi] < 0.10. And when, in the constituent phases of the metallographic structure other than non-metallic inclusions, the area ratio of the α-phase is set as α%, the area ratio of the γ-phase is set as γ%, and the area ratio of the β1-phase as the modified β-phase is set as β1%, the following relationships hold: 30 ≤ f3 = α ≤ 70, 30 ≤ f4 = β1 ≤ 70, 0 ≤ f5 = γ < 1, 35 < f6 = β1 × ([Si] )1 / 2 -γ × 2 + ([Pb] + [Bi]) 1 / 2 × 20 + ([P]) 1 / 2 × 15, with respect to the β1-phase, when etching with a mixed solution of hydrogen peroxide and ammonia water, grain boundaries can be observed.

[0054] The free-cutting copper alloy of aspect 5 of the present invention is characterized in that in the free-cutting copper alloy according to any one of aspects 1 to 4 of the present invention, the free-cutting copper alloy is used for appliances and parts related to drinking water and sanitary equipment, valves, cocks, industrial pipe parts, water meters, musical instruments, automotive parts, electrical and electronic equipment parts, mechanical parts, stationery, toys, sliding parts, measuring instrument parts, precision mechanical parts, and medical parts.

[0055] The manufacturing method of the free-cutting copper alloy according to aspect 6 of the present invention is characterized in that the manufacturing method manufactures the free-cutting copper alloy described in any one of aspects 1 to 4 of the present invention, has one or more hot working processes, and in the final hot working process of the hot working processes, the hot working temperature exceeds 540°C and is less than 750°C. During the cooling process after hot working, cooling treatment of the hot-worked piece starts at a temperature lower than 670°C and higher than 500°C. During the cooling treatment, cooling is performed in such a manner that the average cooling rate in the temperature range from the cooling treatment start temperature to 500°C exceeds 300°C / minute and the average cooling rate in the temperature range from 500°C to 300°C exceeds 300°C / minute.

[0056] The manufacturing method of the free-cutting copper alloy according to aspect 7 of the present invention is characterized in that the manufacturing method manufactures the free-cutting copper alloy described in any one of aspects 1 to 4 of the present invention, has one or more hot working processes and heat treatment processes, and in the final heat treatment process, annealing is performed under the condition of holding at a temperature exceeding 520°C and less than 630°C for 1 minute to 5 hours. After annealing, cooling treatment starts at a temperature higher than 500°C, and cooling is performed in such a manner that the average cooling rate in the temperature range from the cooling treatment start temperature to 500°C exceeds 300°C / minute and the average cooling rate in the temperature range from 500°C to 300°C exceeds 300°C / minute.

[0057] According to one aspect of the present invention, a free-cutting copper alloy and a manufacturing method of the free-cutting copper alloy can be provided. The free-cutting copper alloy has excellent hot workability, good machinability, dezincification corrosion resistance, stress corrosion cracking resistance, high strength, excellent balance between strength and ductility, and a significantly reduced Pb content. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1A It is a micrograph of the structure of the copper alloy in the embodiment, and the copper alloy is obtained by performing process No. A2 on alloy No. S01. Specifically, alloy No. S01 has a composition of Zn - 63.3 mass% Cu - 0.95 mass% Si - 0.069 mass% P - 0.063 mass% Pb - 0.017 mass% Bi. In process No. A2, hot extrusion is performed at 630°C, and cooling treatment starts at 580°C, and the average cooling rate in the temperature range from 580°C to 300°C and the average cooling rate in the temperature range from 500°C to 300°C are both 1020°C / minute.

[0059] Figure 1B is the result of a dezincification corrosion test on the Figure 1A alloy according to the test method of ISO 6509, and it is a cross-sectional metallographic structure photograph including the part showing the maximum corrosion depth.

[0060] Figure 2A It is a micrograph of the structure of the copper alloy in the embodiment. The copper alloy is obtained by performing Process No. E2 on Alloy No. S11. Specifically, Alloy No. S11 has a composition of Zn - 62.5 mass%, Cu - 0.96 mass%, Si - 0.064 mass%, P - 0.072 mass%, and Pb - 0.072 mass%. In Process No. E2, hot extrusion is performed at 550°C, and the average cooling rate in the temperature range from 500°C to 300°C is 20°C / min to obtain a bar with a diameter of 50 mm and a length of 200 mm. The bar is heated, placed horizontally, and hot forged at 680°C to make the thickness 20 mm, and cooling treatment is started at 565°C, and the average cooling rate in the temperature range from 565°C to 300°C and the average cooling rate in the temperature range from 500°C to 300°C are both 900°C / min.

[0061] Figure 2B is the result of a dezincification corrosion test performed on the Figure 2A alloy according to the test method of ISO 6509, and it is a cross-sectional metallographic structure photograph including the part showing the maximum corrosion depth.

[0062] Figure 3A It is a micrograph of the structure of the copper alloy in the embodiment. The copper alloy is obtained by performing Process No. E13H on Alloy No. S11. Specifically, Alloy No. S11 has a composition of Zn - 62.5 mass%, Cu - 0.96 mass%, Si - 0.064 mass%, P - 0.072 mass%, and Pb - 0.072 mass%. In Process No. E13H, hot extrusion is performed at 550°C, and the average cooling rate in the temperature range from 500°C to 300°C is 20°C / min to obtain a bar with a diameter of 50 mm and a length of 200 mm. The bar is heated, placed horizontally, and hot forged at 630°C to make the thickness 20 mm, and cooled at an average cooling rate of 35°C / min. Then, cooling treatment is started at 455°C, and the average cooling rate in the temperature range from 455°C to 300°C is 800°C / min. Figure 3A The alloy of Figure 2A has a different cooling treatment start temperature from the alloy of

[0063] Figure 3B is the result of a dezincification corrosion test performed on the Figure 3A alloy according to the test method of ISO 6509, and it is a cross-sectional metallographic structure photograph including the part showing the maximum corrosion depth.

[0064] Figure 4AIt is a micrograph of the structure of the copper alloy in the embodiment. The copper alloy is obtained by subjecting Alloy No. S43 to Process No. E6. Specifically, Alloy No. S43 has a composition of Zn - 63.3 mass% Cu - 0.98 mass% Si - 0.084 mass% P - 0.060 mass% Pb - 0.28 mass% Sn. In Process No. E6, the casting obtained by casting into a mold die with a diameter of 55 mm is machined to a diameter of 50 mm and cut to a length of 200 mm. The casting is heated, placed horizontally, and hot forged at 630 °C to make the thickness 20 mm. Cooling treatment is started at 565 °C, and the average cooling rate in the temperature range from 565 °C to 300 °C and the average cooling rate in the temperature range from 500 °C to 300 °C are both 900 °C / minute.

[0065] Figure 4B It is the result of a dezincification corrosion test on the Figure 4A alloy according to the test method of ISO 6509, and it is a cross-sectional metallographic structure photograph including the part showing the maximum corrosion depth.

[0066] Figure 5A It is a micrograph of the structure of the copper alloy in the embodiment. The copper alloy is obtained by subjecting Alloy No. S02 to Process No. A34H and Process No. G1. Specifically, Alloy No. S02 has a composition of Zn - 62.9 mass% Cu - 0.98 mass% Si - 0.071 mass% P - 0.071 mass% P. In Process No. A34H, hot extrusion is carried out at 615 °C, and the average cooling rate from 500 °C to 300 °C is 18 °C / minute to obtain the alloy. In Process No. G1, the alloy is further heated at 580 °C for 30 minutes, and cooling treatment is started at 560 °C, and the average cooling rate in the temperature range from 560 °C to 300 °C and the average cooling rate in the temperature range from 500 °C to 300 °C are both 1800 °C / minute.

[0067] Figure 5B It is the result of a dezincification corrosion test on the Figure 5A alloy according to the test method of ISO 6509, and it is a cross-sectional metallographic structure photograph including the part showing the maximum corrosion depth.

[0068] Figure 6AIt is a micrograph of the structure of the copper alloy in the embodiment. The copper alloy is obtained by subjecting Alloy No. S02 to Process No. E14H. Specifically, Alloy No. S02 has a composition of Zn-62.9 mass% Cu-0.98 mass% Si-0.071 mass% P-0.071 mass% Pb. In Process No. E14H, hot extrusion is performed at 550 °C, and the average cooling rate from 500 °C to 300 °C is 20 °C / min to obtain a bar with a diameter of 50 mm and a length of 200 mm. This bar is heated, placed horizontally, and hot forged at 630 °C to make the thickness 20 mm, and then naturally cooled. The average cooling rate in the temperature range from 500 °C to 300 °C is 25 °C / min.

[0069] Figure 6B is the result of a dezincification corrosion test on the Figure 6A alloy according to the test method of ISO 6509, and it is a cross-sectional metallographic structure photograph including the part showing the maximum corrosion depth. Detailed Embodiment

[0070] Hereinafter, an easy-cutting copper alloy and a method for manufacturing the easy-cutting copper alloy according to an embodiment of the present invention will be described.

[0071] Examples of the parts include appliances and supplies related to drinking water and sanitary equipment, musical instruments, tableware, parts of electric / household appliance / electronic equipment, automotive parts, mechanical parts, stationery, precision mechanical parts, medical parts, and appliances and parts related to liquids or gases such as industrial water, drainage, and hydrogen. Specific part names include faucets, mixing faucets, stop faucets, valves, cocks, joints, water meters, gears, sensors, nuts, screws, etc.

[0072] Here, in this specification, an element symbol with parentheses such as [Zn] represents the content (mass%) of the element.

[0073] Moreover, in this embodiment, the composition relationships f1, f2, and f0 are defined as follows for using this content representation method.

[0074] Regarding the composition relationship f1 = [Cu] - 4.6×[Si] + 0.5×([Pb] + [Bi]) - [P], when containing more than 0.05 mass% of Sn, f1 = [Cu] - 4.6×[Si] + 0.5×([Pb] + [Bi]) - [P] - [Sn],

[0075] When containing Bi, the composition relationship f2 = [Pb] + [Bi],

[0076] When containing Sn, f0 = [Sn] / [Si].

[0077] In addition, in the present embodiment, in the constituent phases of the metallographic structure other than non-metallic inclusions, the area fraction of the α-phase is represented by α%, the area fraction of the γ-phase is represented by γ%, the area fraction of the unmodified β-phase is represented by β%, and the area fraction of the β1-phase as the modified β-phase is represented by β1%. The area fraction of each phase is also referred to as the amount of each phase, the proportion of each phase, or the proportion occupied by each phase.

[0078] Moreover, in the present embodiment, a plurality of texture relationships are defined as follows.

[0079] Texture relationship f3 = α

[0080] Texture relationship f4 = β1

[0081] Texture relationship f4A = β

[0082] Texture relationship f5 = γ

[0083] Texture and composition relationship f6 = β1 × ([Si]) 1 / 2 - γ × 2 + ([Pb] + [Bi]) 1 / 2 × 20 + ([P]) 1 / 2 × 15

[0084] The free-cutting copper alloy according to the first embodiment of the present invention is characterized in that it contains more than 60.5% by mass and less than 65.0% by mass of Cu, more than 0.50% by mass and less than 1.20% by mass of Si, 0.002% by mass or more and less than 0.20% by mass of Pb, and more than 0.01% by mass and less than 0.18% by mass of P, and contains, as an optional element, 0.0001% by mass or more and less than 0.20% by mass of Bi, and the balance is composed of Zn and inevitable impurities. In the inevitable impurities, the total content of Fe, Mn, Co, and Cr is less than 0.40% by mass, and the content of Al is less than 0.30% by mass. When the content of Cu is [Cu]% by mass, the content of Si is [Si]% by mass, the content of Pb is [Pb]% by mass, the content of P is [P]% by mass, and the content of Bi is [Bi]% by mass, the following relationships hold: 57.5 ≤ f1 = [Cu] - 4.6 × [Si] + 0.5 × ([Pb] + [Bi]) - [P] ≤ 60.5. When Bi is contained, the following relationship further holds: 0.003 ≤ f2 = [Pb] + [Bi] < 0.20. And when, in the constituent phases of the metallographic structure other than non-metallic inclusions, the area fraction of the α-phase is α%, the area fraction of the γ-phase is γ%, and the area fraction of the β1-phase as the modified β-phase is β1%, the following relationships hold: 20 ≤ f3 = α < 75, 25 < f4 = β1 ≤ 80, 0 ≤ f5 = γ < 4, 27 < f6 = β1 × ([Si]) 1 / 2-γ×2 + ([Pb] + [Bi]) 1 / 2 ×20 + ([P]) 1 / 2 ×15. Regarding the β1 phase, grain boundaries can be observed during etching with a mixed solution of hydrogen peroxide and ammonia water.

[0085] The free-cutting copper alloy according to the second embodiment of the present invention is characterized in that it contains 61.2% by mass or more and 64.8% by mass or less of Cu, 0.65% by mass or more and 1.10% by mass or less of Si, 0.003% by mass or more and less than 0.10% by mass of Pb, and 0.03% by mass or more and 0.15% by mass or less of P, and contains 0.001% by mass or more and less than 0.10% by mass of Bi as an optional element. The balance is composed of Zn and inevitable impurities. In the inevitable impurities, the total content of Fe, Mn, Co, and Cr is less than 0.30% by mass, and the content of Al is less than 0.15% by mass. When the content of Cu is set as [Cu]% by mass, the content of Si is set as [Si]% by mass, the content of Pb is set as [Pb]% by mass, the content of P is set as [P]% by mass, and the content of Bi is set as [Bi]% by mass, the following relationships hold: 58.0 ≤ f1 = [Cu] - 4.6×[Si] + 0.5×([Pb] + [Bi]) - [P] ≤ 60.2. When Bi is contained, the following relationship further holds: 0.004 ≤ f2 = [Pb] + [Bi] < 0.10. And when, in the constituent phases of the metallographic structure other than non-metallic inclusions, the area ratio of the α phase is set as α%, the area ratio of the γ phase is set as γ%, and the area ratio of the β1 phase as the modified β phase is set as β1%, the following relationships hold: 30 ≤ f3 = α ≤ 70, 30 ≤ f4 = β1 ≤ 70, 0 ≤ f5 = γ < 1, 35 < f6 = β1×([Si]) 1 / 2 -γ×2 + ([Pb] + [Bi]) 1 / 2 ×20 + ([P]) 1 / 2 ×15. Regarding the β1 phase, grain boundaries can be observed during etching with a mixed solution of hydrogen peroxide and ammonia water.

[0086] The free-cutting copper alloy of the third embodiment of the present invention is characterized in that it contains Cu of more than 60.5% by mass and less than 65.0% by mass, Si of more than 0.50% by mass and less than 1.20% by mass, Pb of 0.002% by mass or more and less than 0.20% by mass, P of more than 0.01% by mass and less than 0.18% by mass, and Sn of more than 0.05% by mass and less than 0.90% by mass, and contains Bi of 0.0001% by mass or more and less than 0.20% by mass as an optional element. The balance is composed of Zn and inevitable impurities. In the inevitable impurities, the total content of Fe, Mn, Co, and Cr is less than 0.40% by mass, and the content of Al is less than 0.30% by mass. When the content of Cu is set as [Cu]% by mass, the content of Si is set as [Si]% by mass, the content of Pb is set as [Pb]% by mass, the content of P is set as [P]% by mass, the content of Bi is set as [Bi]% by mass, and the content of Sn is set as [Sn]% by mass, it has the following relationship: 57.5 ≤ f1 = [Cu] - 4.6 × [Si] + 0.5 × ([Pb] + [Bi]) - [P] - [Sn] ≤ 60.5, and further has the following relationship: f0 = [Sn] / [Si] < 1. When Bi is contained, it has the following relationship: 0.003 ≤ f2 = [Pb] + [Bi] < 0.20. And when, in the constituent phases of the metallographic structure other than non-metallic inclusions, the area ratio of the α-phase is set as α%, the area ratio of the γ-phase is set as γ%, and the area ratio of the β1-phase, which is a modified β-phase, is set as β1%, it has the following relationships: 20 ≤ f3 = α < 75, 25 < f4 = β1 ≤ 80, 0 ≤ f5 = γ < 4, 27 < f6 = β1 × ([Si]) 1 / 2 -γ × 2 + ([Pb] + [Bi]) 1 / 2 × 20 + ([P]) 1 / 2 × 15. Regarding the β1-phase, when etched with a mixed solution of hydrogen peroxide and ammonia water, grain boundaries can be observed in the β1-phase.

[0087] The free-cutting copper alloy according to the fourth embodiment of the present invention is characterized in that it contains Cu in an amount of 61.2% by mass or more and 64.8% by mass or less, Si in an amount of 0.65% by mass or more and 1.10% by mass or less, Pb in an amount of 0.003% by mass or more and less than 0.10% by mass, P in an amount of 0.03% by mass or more and 0.15% by mass or less, and Sn in an amount of 0.10% by mass or more and less than 0.50% by mass, and contains Bi in an amount of 0.001% by mass or more and less than 0.10% by mass as an optional element. The balance is composed of Zn and inevitable impurities. In the inevitable impurities, the total content of Fe, Mn, Co, and Cr is less than 0.30% by mass, and the content of Al is less than 0.15% by mass. When the content of Cu is set as [Cu]% by mass, the content of Si is set as [Si]% by mass, the content of Pb is set as [Pb]% by mass, the content of P is set as [P]% by mass, the content of Bi is set as [Bi]% by mass, and the content of Sn is set as [Sn]% by mass, the following relationships hold: 58.0 ≤ f1 = [Cu] - 4.6×[Si] + 0.5×([Pb] + [Bi]) - [P] - [Sn] ≤ 60.2, and further the following relationship holds: f0 = [Sn] / [Si] < 0.6. When Bi is contained, the following relationship holds: 0.004 ≤ f2 = [Pb] + [Bi] < 0.10, and when, in the constituent phases of the metallographic structure other than non-metallic inclusions, the area ratio of the α-phase is set as α%, the area ratio of the γ-phase is set as γ%, and the area ratio of the β1-phase, which is a modified β-phase, is set as β1%, the following relationships hold: 30 ≤ f3 = α ≤ 70, 30 ≤ f4 = β1 ≤ 70, 0 ≤ f5 = γ < 1, 35 < f6 = β1×([Si] )1 / 2 -γ×2 + ([Pb] + [Bi]) 1 / 2 ×20 + ([P]) 1 / 2 ×15, with respect to the β1-phase, when etched with a mixed solution of hydrogen peroxide and ammonia water, grain boundaries can be observed.

[0088] Hereinafter, the reasons for specifying the component composition, the composition relationships f0, f1, f2, the structure relationships f3, f4, f5, the structure and composition relationship f6, the metallographic structure, etc. as described above will be described.

[0089] <Component Composition>

[0090] (Cu)

[0091] Cu is the main element of the free-cutting copper alloy of this embodiment. To overcome the problems of the present invention, it is necessary to contain at least more than 60.5% by mass of Cu. When the Cu content is 60.5% by mass or less, although it also depends on the contents of Si, Zn, P, Pb, Bi, Sn and the manufacturing process, the proportion of the β1 phase exceeds 80%, and the ductility will decrease. Moreover, the modification of the β phase is not fully carried out, resulting in poor dezincification corrosion resistance, stress corrosion cracking resistance and machinability. Therefore, the lower limit of the Cu content exceeds 60.5% by mass, preferably 61.2% by mass or more, more preferably 61.5% by mass or more, and further preferably 62.0% by mass or more.

[0092] On the other hand, when the Cu content is 65.0% by mass or more, although it also depends on the contents of Si, Zn, P, Pb, Bi, Sn and the manufacturing process, the proportion of the β1 phase becomes smaller. As a result, excellent machinability cannot be obtained and the strength also decreases. Therefore, the Cu content is less than 65.0% by mass, preferably 64.8% by mass or less, more preferably 64.5% by mass or less.

[0093] (Si)

[0094] Si is the main element of the free-cutting copper alloy of this embodiment. Si contributes to the formation of metal phases such as κ phase, γ phase, μ phase, β phase, β1 phase, ζ phase, etc. By containing Cu, Zn, Si and P in the above ranges and additional processes, the β phase is modified, and the β1 phase is generated through the following specific cooling treatment. The machinability is improved by the β1 phase (modified β phase), and at the same time, the disadvantages of the conventional β phase, namely dezincification corrosion resistance and stress corrosion cracking resistance, are greatly improved. As a representative composition of the modified β1 phase, Cu is about 61% by mass, Si is about 1.2% by mass, Zn is about 37.5% by mass, and P is about 0.1% by mass.

[0095] On the other hand, regarding the α phase, as a representative composition, Cu is about 66% by mass, Si is about 0.7% by mass, and Zn is about 33% by mass. In the composition range of this embodiment, the machinability of the α phase is slightly improved by containing Si, and the dezincification corrosion resistance and stress corrosion cracking resistance of the α phase are improved by containing Si. Moreover, through the modified β1 phase and the improved α phase, the dezincification corrosion resistance and stress corrosion cracking resistance of the alloy are particularly improved.

[0096] In addition, a certain amount of α phase is required to modify the β phase. For example, when there is no α phase at all, the β phase will not be modified. To improve the dezincification corrosion resistance, stress corrosion cracking resistance, ductility and machinability of the alloy, the α phase needs to be 20% or more, preferably 30% or more in terms of area ratio.

[0097] Si is an essential element for modifying the β phase into the β1 phase. The more Si there is, the more the β phase can be modified, thus becoming the β1 phase with more excellent properties. In order to modify the β phase and make it more the modified β1 phase, it is necessary to contain more than 0.50% by mass of Si. The Si content is preferably 0.60% by mass or more, more preferably 0.65% by mass or more, and further preferably 0.75% by mass or more.

[0098] On the other hand, when the amount of Si reaches a specific amount, the modification of the β1 phase will saturate. Further, if the content of Si is too much, the conductivity will decrease. Depending on the situation, the γ phase will appear, resulting in poor dezincification corrosion resistance, stress corrosion cracking resistance, and machinability. However, in Patent Documents 2-8, it is considered that the γ phase can improve the machinability. However, in the present application mainly composed of the β1 phase and the α phase, the presence of the γ phase will instead deteriorate the machinability, reduce the ductility of the alloy, and result in poor dezincification corrosion resistance and stress corrosion cracking resistance. Therefore, it is preferable to limit the amounts of Si and the γ phase. From this, it can be seen that the amount of Si is less than 1.20% by mass, preferably 1.10% by mass or less. If conductivity is emphasized, the amount of Si is 1.0% by mass or less.

[0099] (Zn)

[0100] Zn, together with Cu and Si, is a main constituent element of the free-cutting copper alloy of the present embodiment, and is an element required to improve machinability, strength, high-temperature properties, and castability. In addition, Zn is the remainder, but if an explanation is forced, the Zn content is less than about 38.5% by mass, preferably less than 38.0% by mass, and more than about 32.0% by mass, preferably more than 33.0% by mass.

[0101] (P)

[0102] Similar to Si, P is an essential element for modifying the β phase into the β1 phase. During hot working, P dissolves in the β phase. When cooling is carried out after hot working, cooling treatment is started at a temperature exceeding 500°C and lower than 670°C, and within the temperature range from the cooling treatment start temperature to 500°C and the temperature range from 500°C to 300°C, cooling is carried out at a cooling rate exceeding 300°C / minute. Thus, the β phase is modified into the β1 phase, and the β1 phase is obtained. The modification from the β phase to the β1 phase greatly improves the problems of the conventional β phase, namely, dezincification corrosion resistance and stress corrosion cracking resistance. At the same time, due to the presence of the β1 phase, the cutting resistance can be reduced during cutting, thereby improving chip breakability. However, the compound containing P reduces the cutting resistance, resulting in better chip breakability. But if cooling treatment is started at a cooling rate exceeding 300°C / minute from a temperature exceeding about 550°C or 530°C, the compound containing P does not exist or exists in a small amount. From the viewpoint of improving machinability, the effect of the modification from the β phase to the β1 phase exceeds the effect of the compound containing P existing in the β phase. Especially when the cutting speed is faster than about 100 m / minute, better machinability can be obtained in the case where the β phase is modified into the β1 phase compared with the case where the compound containing P exists in the β phase. In addition, the dezincification corrosion resistance and stress corrosion cracking resistance of the α phase are improved by containing P, thereby greatly improving the dezincification corrosion resistance and stress corrosion cracking resistance of the alloy composed of the β1 phase and the α phase.

[0103] In order to modify the β phase into the β1 phase, the lower limit of the P content needs to exceed at least 0.01 mass%. Considering more excellent modification into the β1 phase, the amount of the following inevitable impurities, the cooling treatment start temperature, and the cooling rate after the start of the cooling treatment, the P content is preferably 0.03 mass% or more, and more preferably 0.04 mass% or more.

[0104] In addition, P easily forms compounds with Zn, Si, Mn, Fe, Cr, Co, Al, etc. If P forms a compound and the P in the β phase dissolved in the alloy after hot working decreases, the modification of the β phase into the β1 phase will be hindered. The formation of the compound of Zn and Si, which are the main elements of the alloy in this application, with P starts at about 550°C. If the cooling rate becomes slower, the amount of the P compound will increase. The formation of the compound of Mn, Fe, Cr, Co, which are inevitable impurities, with P starts at a temperature exceeding about 550°C. If their amounts increase, the formation of the P compound will be further promoted. That is, the presence of Mn, Fe, Cr, Co hinders the modification into the β1 phase, resulting in an increase in the cutting resistance of the alloy, poor chip breakability, and poor dezincification corrosion resistance and stress corrosion cracking resistance. Therefore, the total content of at least Fe, Mn, Co, and Cr needs to be less than 0.40 mass%, and preferably less than 0.30 mass%.

[0105] The formation of the compound of P with Zn and Si has a positive effect on machinability, but is contrary to the modification of the β phase to the β1 phase and the existence of the compound of P with Zn and Si. As described above, in order to form the β1 phase, after hot working, cooling treatment is started at a temperature exceeding 500°C and lower than 670°C, and the cooling rate in the temperature range from the cooling treatment start temperature to 300°C is accelerated. In contrast, in order to fully form the compound of P with Zn and Si, it is necessary to slowly cool in the temperature range of about 530°C to about 450°C. Therefore, when more P compounds are formed, the formation of the β1 phase will be slightly insufficient, that is, the modification of the β phase will be slightly insufficient. Or sometimes the β1 phase does not exist.

[0106] On the other hand, even when P is contained in an amount of 0.18 mass% or more, the effect of forming the β1 phase has saturated, and instead, due to the influence of P dissolved in the β1 phase, the ductility or conductivity decreases. Therefore, the content of P is less than 0.18 mass%, preferably 0.15 mass% or less, and more preferably 0.12 mass% or less.

[0107] (Pb)

[0108] In the present embodiment, good machinability of the alloy is obtained through the β1 phase containing Si and P, and the machinability is further improved by containing a small amount of Pb. In the composition of the present embodiment, about 0.001 mass% of Pb is dissolved in the matrix, and Pb in excess of this amount exists as fine Pb particles having a diameter of about 0.1 to about 2 μm. Generally, it is considered that containing about 0.1 mass% of Pb is hardly helpful for improving machinability. For example, in ASM Specialty Handbook, Copper and Copper Alloys, published in August 2001, first edition, page 267, Figure 6, the relationship between the amount of Pb and machinability when the machinability of a Cu-Zn-Pb alloy containing 62 to 65 mass% of Cu, containing about 3.2 mass% of Pb, and the balance being composed of Zn is set to 100% is shown, indicating that containing 0.1 mass% of Pb has an effect of only increasing the machinability by about 5%, that is, increasing from about 25% to about 30% in terms of the machinability index. On the other hand, in the present application, even if Pb is in a trace amount, it has a significant effect on machinability and exhibits an effect with a content of 0.002 mass% or more. The Pb content is preferably 0.003 mass% or more, and more preferably 0.01 mass% or more. Further, when the cutting conditions become severe, such as when the cutting speed is increased, the feed rate is increased, the cutting depth is increased, the drill hole diameter is increased, etc., the Pb content is preferably 0.03 mass% or more. By containing the β1 phase with greatly improved machinability and a small amount of Pb, the machinability of the alloy is greatly improved.

[0109] As is well known, Pb improves the machinability of copper alloys. Therefore, in a binary Cu-Zn alloy represented by free-cutting brass rod C3604, about 3 mass% of Pb is required. In the present embodiment, an alloy having excellent machinability is formed by making β1 phase containing Si and P, trace Pb particles, or the following Pb and Bi particles present in the metallographic structure. On the other hand, since Pb is harmful to the human body, the upper limit of Pb is set to less than 0.20 mass%. Further, the Pb content is preferably less than 0.10 mass%, and optimally 0.08 mass% or less in view of the impact on the human body or the environment.

[0110] (Bi)

[0111] Similar to Pb, Bi is dissolved in the matrix in an amount of about 0.0001 mass%, and Bi exceeding this amount exists as particles with a diameter of about 0.1 to about 2 μm. When both Pb and Bi are added, most of them exist as particles with a diameter of about 0.1 to about 2 μm formed by mixing Pb and Bi. In the present embodiment, it is known that by containing Bi and Pb together on the premise that the β1 phase exists, machinability equivalent to or higher than that in the case of separately containing Pb and Bi can be obtained. It is considered that the function of Bi to improve machinability is inferior to that of Pb, but it has been found through research that in the present embodiment, it exhibits the same effect as Pb and, in some cases, an effect exceeding that of Pb. However, Bi deteriorates the stress corrosion cracking resistance of brass, but if it exists as particles formed by mixing Pb and Bi or the amount of Bi is small, it has almost no influence on stress corrosion cracking.

[0112] When Bi is contained, in order to have good machinability of the alloy, at least 0.0001 mass% or more of Bi is required. The content of Bi is preferably 0.001 mass% or more, and more preferably 0.002 mass% or more. The impact of Bi on the human body is not clear at present stage, but the amount of Bi is set to less than 0.20 mass%, preferably less than 0.10 mass%, and further preferably 0.08 mass% or less. In addition, as described above, in the present embodiment, considering that Bi can sufficiently replace Pb, the impact of Bi on the human body is unclear, Bi is one of the rare metals and will affect the environment and is included as an inevitable impurity in the raw materials, Bi can be contained as an optional element or not. Further, in view of the impact on the human body or the environment and the impact on stress corrosion cracking, the total content of Pb and Bi (the following compositional relationship formula f2) is set to less than 0.20 mass%, preferably less than 0.10 mass%. Thus, in the present embodiment, depending on the situation, the amount of Pb (including Bi) harmful to the human body is limited to less than 0.20 mass%, and the target is excellent machinability.

[0113] (Sn)

[0114] By dissolving Sn in the β1 phase, the dezincification corrosion resistance of the β1 phase is further improved, thereby enhancing the dezincification corrosion resistance of the alloy. When Sn is contained, in order to achieve this effect, it is necessary to contain more than 0.05% by mass of Sn, preferably 0.10% by mass or more. However, compared with the α phase, Sn is originally more partitioned into the β phase and the β1 phase. By containing a small amount of Sn, the dezincification corrosion resistance is improved. However, if the Sn concentration is high, it is easy to form the γ phase, resulting in a decrease in ductility. The formation of the γ phase not only causes a decrease in the ductility of the alloy but also reduces the machinability and the dezincification corrosion resistance deteriorates. Although it is also related to the Si content, the Sn content needs to be maintained at less than 0.90% by mass, preferably less than 0.70% by mass, and more preferably less than 0.50% by mass.

[0115] As described above, Sn is more partitioned into the β phase and the β1 phase. As a result, it can be seen that if the Sn content is high, there may sometimes be problems with the modification of the β phase containing Si and P. Specifically, it has been found that if the amount of Sn is more than the amount of Si, the modification of the β phase is insufficient, and the effect of improving the dezincification corrosion resistance by containing Sn is offset. As described below, it is necessary to make the Si content exceed the Sn content.

[0116] (Inevitable impurities, especially Fe, Mn, Co, and Cr / Al)

[0117] Examples of the inevitable impurities in the present embodiment include Mn, Fe, Al, Ni, Mg, Se, Te, Sn, Bi, Co, Ca, Zr, Cr, Ti, In, W, Mo, B, Ag, and rare earth elements, etc.

[0118] In the past, in free-cutting copper alloys, particularly free-cutting brass containing Zn in an amount of about 30% by mass or more, high-quality raw materials such as electrolytic copper and electrolytic zinc were not the main raw materials, but recycled copper alloys were the main raw materials. In the downstream processes (downstream processes, machining processes) in this field, most components and parts are machined, and a large amount of waste copper alloy is generated at a ratio of 40 to 80 (parts by mass) relative to 100 (parts by mass) of the material. Examples include chips, scraps, burrs, runners, and products with manufacturing defects. These waste copper alloys are the main raw materials. If the classification of chips, scraps, etc. is not sufficient, Pb, Fe, Mn, Si, Se, Te, Sn, P, Sb, As, Bi, Ca, Al, Zr, Ni, and rare earth elements will be mixed in as raw materials from free-cutting brass containing Pb, free-cutting copper alloys without Pb but containing Bi, etc., or special brass alloys containing Si, Mn, Fe, Al, and other copper alloys. Also, Fe, W, Co, Mo, etc. mixed in from the tool are contained in the chips. Since electroplated products are included in the waste products to be recycled, Ni and Cr are mixed in. Also, in pure copper-based scrap used in place of electrolytic copper, Mg, Sn, Fe, Cr, Ti, Co, In, Ni, and Se are mixed in. In brass-based scrap used in place of electrolytic copper or electrolytic zinc, there are often cases of Sn plating, so Sn is mixed in.

[0119] Considering aspects of resource recycling and cost issues, waste materials containing these elements within a range that at least does not have an adverse effect on the properties are used as raw materials. Additionally, in free-cutting brass rod C3604 with Pb added in accordance with Japanese JIS specifications (Japanese JIS H 3250), the essential element Pb is contained in an amount of about 3% by mass, and further, as an impurity, Fe is allowed to be 0.5% by mass or less, and Fe + Sn (the total amount of Fe and Sn) is allowed up to 1.0% by mass. In fact, sometimes the free-cutting brass rod contains a high concentration of Fe or Sn.

[0120] Fe, Mn, Co, and Cr dissolve in the α-phase and β-phase of the Cu-Zn alloy to a certain concentration. However, if Si or P is present at this time, they are likely to combine with Si or P, which may consume the Si or P required for β-phase modification. Moreover, Fe, Mn, Co, and Cr that combine with Si form Fe-Si compounds, Mn-Si compounds, Co-Si compounds, Cr-Si compounds, etc. in the metallographic structure. Similarly, Fe, Mn, Co, and Cr that combine with P form Fe-P compounds, Mn-P compounds, Co-P compounds, Cr-P compounds, etc. in the metallographic structure. These intermetallic compounds are very hard, so they not only increase the cutting resistance but also shorten the tool life. Therefore, the amounts of Fe, Mn, Co, and Cr need to be restricted in advance. The content of each is preferably less than 0.30 mass%, more preferably less than 0.20 mass%, and further preferably 0.15 mass% or less. In particular, the total content of Fe, Mn, Co, and Cr needs to be less than 0.40 mass%, preferably less than 0.30 mass%, more preferably less than 0.25 mass%, and further 0.20 mass% or less.

[0121] On the other hand, if the content of Al mixed in from special brass rods, brass castings, etc. increases, it will affect the modification of the β-phase, and Al forms compounds with P or Si, so it needs to be restricted. In the alloy of this embodiment, the content of Al needs to be less than 0.30 mass%, preferably less than 0.15 mass%, and further preferably 0.10 mass% or less.

[0122] As other major inevitable impurity elements, empirically, Ni mostly mixes in from waste materials, etc. The influence of Ni on mechanical properties such as machinability is relatively small, but considering its influence on the human body, it needs to be restricted. The content of Ni is preferably less than 0.20 mass%, more preferably less than 0.10 mass%. Regarding Ag, Ag is generally regarded as Cu and has almost no influence on each property, so there is no special restriction, but the Ag content is preferably less than 0.05 mass%. Te and Se themselves have good machinability and may be mixed in large amounts although they are rare. Considering their influence on ductility or impact properties, the content of Te and Se is preferably less than 0.10 mass%, more preferably less than 0.05 mass%, and further preferably 0.02 mass% or less. Moreover, As or Sb is included in corrosion-resistant brass to improve the corrosion resistance of brass, but considering their influence on ductility and the human body, the content of As and Sb is preferably less than 0.05 mass%, more preferably 0.02 mass% or less.

[0123] The content of other elements such as Mg, Ca, Zr, Ti, In, W, Mo, B, and rare earth elements is preferably less than 0.05 mass%, more preferably less than 0.03 mass%, and further preferably 0.02 mass% or less.

[0124] In addition, the content of rare earth elements is the total amount of one or more of Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Tb, and Lu.

[0125] Regarding the inevitable impurities other than Fe, Mn, Co, Cr, and Al as described above, the total amount is preferably less than 0.70% by mass, and more preferably less than 0.50% by mass.

[0126] (Composition relationship f1)

[0127] Regarding the composition relationship f1 = [Cu] - 4.6×[Si] + 0.5×([Pb] + [Bi]) - [P] - [Sn], when the content of Sn is 0.05% by mass or less, [Sn] in f1 is 0, and when Bi is not contained, [Bi] in f1 is 0. When Sn is 0.05% by mass or less, the influence on the composition relationship f1 is small, so it is not specified in the composition relationship f1.

[0128] f1 is a formula representing the relationship between the composition and the metallographic structure. Even if the amounts of the respective elements are within the ranges specified above, if the composition relationship f1 is not satisfied, the respective characteristics targeted by the present embodiment cannot be satisfied. If the composition relationship f1 is less than 57.5, the proportions of the β phase and the β1 phase increase, and the modification of the β phase is insufficient, resulting in poor ductility, dezincification corrosion resistance, and stress corrosion cracking resistance.

[0129] Therefore, the lower limit of the composition relationship f1 is 57.5 or more, preferably 58.0 or more, and more preferably 58.2 or more. As the composition relationship f1 becomes a more preferred range, the proportion of the α phase increases, and the modification of the β phase becomes sufficient, so that excellent machinability can be maintained, and good dezincification corrosion resistance and stress corrosion cracking resistance can be obtained, thereby obtaining good ductility and cold workability.

[0130] On the other hand, the upper limit of the composition relationship f1 affects the proportions of the β phase and the β1 phase. If the composition relationship f1 is greater than 60.5, the proportion of the β1 phase decreases, excellent machinability cannot be obtained, and the strength also decreases. Therefore, f1 is 60.5 or less, preferably 60.2 or less, and more preferably 60.0 or less.

[0131] (Composition relationship f2)

[0132] Bi is an optional element that substitutes for the function of Pb. However, when Bi is included, the relational expression 0.003 ≤ f2 = [Pb] + [Bi] < 0.20 must be satisfied. That is, considering that the impact of Bi on the human body is not clear at this stage, Bi is one of the rare metals and can affect the environment, the total amount of Pb and Bi needs to be restricted. When Bi is included, the total amount of Pb and Bi is less than the upper limit of the Pb content, which is 0.20% by mass, preferably less than 0.10% by mass. On the other hand, in order to obtain good machinability, when Bi is included, the total amount of Pb and Bi needs to be 0.003% by mass or more, preferably 0.004% by mass or more, and more preferably 0.005% by mass or more.

[0133] (Composition relational expression f0)

[0134] Sn is contained to further improve dezincification corrosion resistance. The β phase contains more Sn. The more the amount of Sn, the more the progress of dezincification corrosion of the β1 phase is delayed. On the other hand, if the amount of Sn is more than the amount of Si, it will hinder the modification of the β phase, and thus may damage the dezincification corrosion resistance of the β1 phase.

[0135] That is, if f0 = [Sn] / [Si] is set, then f0 needs to be less than 1 in order to exert the effect consistent with containing Sn in consideration of other characteristics. f0 is preferably less than 0.8, more preferably less than 0.6, and further preferably less than 0.5.

[0136] The free-cutting copper alloy of the present embodiment contains a relatively large amount of the conventional β phase, which is the β1 phase in this application. At the same time, it has good dezincification corrosion resistance, stress corrosion cracking resistance, and mechanical properties, and has the completely opposite characteristics of cutting properties and ductility that require a certain brittleness to reduce the resistance during cutting and make the chips break finer. In order to have good corrosion resistance, cutting properties, and mechanical properties, not only the composition of each component is discussed in detail, but also the composition relational expressions f0, f1, f2 and the following structure relational expressions f3 to f5, and the structure and composition relational expression f6 are discussed in detail. Thus, an alloy more suitable for the purpose or use can be provided.

[0137] In addition, regarding Fe, Mn, Co, Cr, Al, and other inevitable impurities that are separately specified, if they are within the range regarded as inevitable impurities, the influence on the composition relational expression f1 is small, so they are not specified in the composition relational expression f1.

[0138] (Comparison with patent documents)

[0139] Here, the results of comparing the compositions of the Cu-Zn-Si alloys described in the above patent documents 1 to 15 with the alloy of the present embodiment are shown in Tables 1 to 4.

[0140]

[0141]

[0142]

[0143]

[0144] In this embodiment, the contents of the main elements Si and Cu are different from those in Patent Document 8. In this embodiment, the content of the main element Si is different from that in Patent Document 9. In this embodiment, the content of the main element Cu is different from that in Patent Document 15.

[0145] In Patent Documents 1, 13, and 15, Pb is not contained, and the Pb contents are different.

[0146] In Patent Documents 8, 10, 11, and 12, from the viewpoints of machinability, dezincification corrosion resistance, corrosion resistance, etc., the β-phase in the metallographic structure is greatly restricted. The β1-phase of this application is different from the β-phase of Patent Documents 8, 10, 11, and 12, but the respective β-phases are 5% or less, 25% or less, 15% or less, and 0.9% or less.

[0147] Patent Document 10 relates to a near-net-shaped tubular hot forging product that uses a tubular blank.

[0148] In Patent Documents 1 and 9, in order to reduce the β-phase and to divide the β-phase, heat treatment is performed at a temperature of 350 to 550°C or 400 to 600°C.

[0149] In Patent Document 9, Sn is contained in an amount of 0.2% by mass or more. Sn and Si are contained to improve the dezincification corrosion resistance of the β-phase. Hot extrusion is performed at a temperature of 700°C or higher to improve machinability, and heat treatment at 400 to 600°C is required to improve corrosion resistance. The proportion of the β-phase is approximately 5 to 20%, the Si content is 0.01 to 0.50% by mass, and it can be controlled to be 0.2% by mass or less.

[0150] In Patent Documents 12, 13, and 14, Al is necessary to improve discoloration resistance, castability, and dezincification corrosion resistance.

[0151] In Patent Document 14, in order to improve dezincification corrosion resistance, Sn and Al are contained in amounts of at least 0.1% by mass or more respectively. In order to obtain excellent machinability, a large amount of Pb and Bi need to be contained.

[0152] In Patent Document 15, the corrosion-resistant copper alloy casting does not contain Pb, requires the γ-phase, contains 65% by mass or more of Cu, and contains Si, and also contains trace amounts of Al, Sb, Sn, Mn, Ni, B, etc., and thus has good mechanical properties and castability.

[0153] Patent Documents 2 to 7 must all be processed such that the average cooling rate in the temperature range of from about 530°C to about 450°C is about 0.1°C / minute or more and about 70°C / minute or less during the cooling process after hot working. As a result, the formed P compound is present in the metallographic structure. Further, the γ phase is useful for machinability, and there is no modification of the β phase at all. There is no introduction of dezincification corrosion resistance and stress corrosion cracking resistance, and no disclosed information. Furthermore, except for Patent Document 7, there is no disclosed information related to cutting resistance under high-speed cutting conditions. In the present application, during the cooling process after hot working, the cooling treatment is started at a temperature lower than 670°C and higher than 500°C, and the average cooling rate in the temperature range from the cooling treatment start temperature to 500°C and the average cooling rate in the temperature range from 500°C to 300°C exceed 300°C / minute, and cooling is carried out in a manner substantially opposite to that of Patent Documents 2 to 7.

[0154] The greatest apparent difference between the present application and Patent Documents 2 to 7 is that in any of Patent Documents 2 to 7, there is no mention at all of the modification of the β phase and the modified β phase, i.e., the β1 phase. The β1 phase is formed under the following conditions. During hot working, a β phase in which a certain amount of Si and P are dissolved is formed. Then, the cooling treatment is started at a temperature higher than 500°C, and during the cooling treatment, cooling is carried out such that the average cooling rate in the temperature range from the cooling treatment start temperature to 500°C exceeds 300°C / minute and the average cooling rate in the temperature range from 500°C to 300°C exceeds 300°C / minute. The β1 phase is formed in the above manner. Then, when etching is carried out using a mixed solution of hydrogen peroxide and ammonia water, if it is the β1 phase, grain boundaries can be observed within the β1 phase, but even if it contains a certain amount of Si and P and is still the β phase before modification, no grain boundaries are observed within the β phase. In Patent Documents 2 to 7, the metallographic structure obtained by etching using a mixed solution of hydrogen peroxide and ammonia water is disclosed, but no grain boundaries are observed within the β phase. Patent Documents 2 to 7 do not define the start temperature of the cooling treatment after hot working, but even if the start temperature of the cooling treatment is lower than 530°C, since the average cooling rate from the start temperature of the cooling treatment to 500°C is about 0.1°C / minute or more and about 70°C / minute or less, the β1 phase (modified β phase) is not observed either.

[0155] Different from the conventional β phase, the dezincification corrosion resistance and stress corrosion cracking resistance of the β1 phase are greatly improved, the machinability is further improved, and it exceeds the machinability when the P compound is present. However, for this purpose, the β1 phase needs to be present in the metallographic structure at an area ratio exceeding 25%. Further, in the present application, the presence of the γ phase impairs the machinability, but in Patent Documents 2 to 7, the γ phase is useful for machinability.

[0156] <Metallographic structure>

[0157] In the Cu-Zn-Si alloy, there are more than 10 phases, which causes complex phase changes. It may not be possible to obtain the target properties only by using the composition range and the relational expressions of the elements. The target properties can be obtained by finally specifying and determining the types of phases existing in the metallographic structure and the range of their area ratios. Therefore, the tissue relational expressions are defined as follows.

[0158] 20 ≤ f3 = α < 75,

[0159] 25 < f4 = β1 ≤ 80, where the β1 phase is a modified β phase.

[0160] 0 ≤ f5 = γ < 4

[0161] (β1 phase)

[0162] Regarding the metallographic structure of this application, except for non-metallic inclusions, it is composed of the α phase, the β1 phase, and a small amount or 0% of the γ phase depending on the situation.

[0163] The difference between the β phase and the β1 phase is that, for the β1 phase, when etched with a mixed solution of hydrogen peroxide and ammonia water, a grain boundary pattern, i.e., grain boundaries, is observed within the β1 phase, but when it is the β phase, no grain boundaries are observed within the β phase.

[0164] The β1 phase in this embodiment is obtained in the following manner: During hot working, an amount of Si and P above a certain level is dissolved in the β phase at a high temperature. Then, it is maintained at a temperature of 500 - 670 °C and cooled (cooling is carried out in such a way that the average cooling rate in the temperature range from the start temperature of the cooling treatment to 500 °C and the average cooling rate in the temperature range from 500 °C to 300 °C both exceed 300 °C / minute, and cooling is continued until it approaches room temperature) to restore the state of the metallographic structure at 500 - 670 °C to room temperature. Specifically, the cooling rate in the temperature range from the high-temperature cooling start temperature to 300 °C is increased for rapid cooling to cool to room temperature below 100 °C. Thus, the state of the metallographic structure at high temperature is restored to room temperature. As a result, the β1 phase is obtained. For the β phase of a Cu-Zn alloy that does not contain both a specific amount of Si and P, the β1 phase cannot be obtained even after this cooling treatment. Similarly, even if an alloy containing Si and P is cooled at a cooling rate exceeding 300 °C / minute from a temperature below 500 °C, such as 450 °C, the β1 phase cannot be obtained. Additionally, modification of the β phase requires a specific amount or more of the α phase. When the α phase is absent or less, the β1 phase cannot be obtained. Further, the degree of modification of the β phase is also affected by the amounts of Si and P, the amount of inevitable impurities, the cooling treatment start temperature, the average cooling rate in the temperature range from the start of the cooling treatment to 500 °C, and the average cooling rate in the temperature range from 500 °C to 300 °C. If the degree of modification of the β phase increases, that is, if more of the β1 phase is modified, a material with better machinability and good dezincification corrosion resistance and stress corrosion cracking resistance can be obtained. Although it also depends on the amount of inevitable impurities such as Fe, the degree of modification of the β phase generally starts to saturate when the Si content is about 1 mass% and the P content is about 0.1 mass%. If their amounts are too large, drawbacks such as a decrease in conductivity or ductility and the appearance of the γ phase may occur.

[0165] The β1 phase (modified β phase) can overcome the shortcomings and main problems of the β phase of the Cu-Zn alloy, namely the dezincification corrosion resistance and stress corrosion cracking resistance of the alloy. That is, as an example, if expressed in specific numbers, the corrosion progress of dezincification corrosion can be reduced by about 60% or more, and similarly, the crack progress of stress corrosion cracking can be delayed by about 50% or more. As described in the patent literature, the dezincification corrosion problem of the Cu-Zn alloy containing the β phase is significant. Since dezincification corrosion occurs along the β phase, the amount of the β phase is limited to 25% or less or 20% or less, and heat treatment at 350 - 550 °C is carried out to further reduce the amount of the β phase and break up the β phase.

[0166] In terms of strength, it largely depends on the area ratio of the constituent phases. However, the strength of the modified β phase, that is, the β1 phase, is higher than that of the β phase, and it has better ductility than the β phase. Therefore, the strength-ductility balance of the alloy is good.

[0167] (β1 phase, structure relationship formula f4)

[0168] In the Cu-Zn-Si-P-Pb alloy which is a free-cutting copper alloy of the present embodiment, it is necessary that the area ratio of the β1 phase exceeds 25% at least, so that the Pb content is the minimum amount and the machinability is good. Further, in order to improve the machinability and strength, the area ratio of the β1 phase is preferably 30% or more, and more preferably 33% or more. On the other hand, if the β1 phase is excessive, for example, 95%, the β phase will not be modified. Since the modification of the β phase is carried out in the presence of the α phase, a certain amount of the α phase is required. Further, regarding dezincification corrosion and stress corrosion cracking, compared with the β phase, the β1 phase can greatly delay the progress of dezincification corrosion and stress corrosion cracking, but the dezincification corrosion resistance and stress corrosion cracking resistance are still inferior to those of the α phase. Specifically, regarding dezincification corrosion, when performing the dezincification corrosion test of ISO 6509, when the metallographic structure is composed of the α phase and the β phase (unmodified β phase), the β phase is selectively dezincified, and the dezincification corrosion depth reaches about 500 μm. When the metallographic structure is composed of the α phase and the β1 phase (modified β phase), although the β1 phase is selectively dezincified, its dezincification corrosion depth is about 20 to about 200 μm, which depends on the modification degree to the β1 phase or the area ratio of the β1 phase, and the progress of dezincification corrosion is greatly inhibited. Thus, by modifying the β phase into the β1 phase, the dezincification corrosion resistance is greatly improved, but even if it is improved, the dezincification corrosion resistance and ductility are still inferior to those of the α phase. Therefore, if the area ratio of the β1 phase is high, the dezincification corrosion resistance and ductility of the alloy will decrease. Based on the above, through in-depth research, it is found that the area ratio of the β1 phase needs to be set to 80% or less, preferably 70% or less, and more preferably 65% or less.

[0169] (α phase, structure relationship formula f3)

[0170] This application is basically composed of an α-phase and a β1-phase. Although a treatment for modifying the β-phase into the β1-phase is carried out, the α-phase is hardly affected by this treatment. Moreover, in order to modify the β-phase, a certain amount or more of the α-phase is required. Also, if the β1-phase is excessive, there is a problem with the ductility of the alloy, and an appropriate amount of ductile α-phase is needed. On the contrary, if the α-phase is excessive, the strength will decrease. And, compared with the α-phase without Si, the machinability of the α-phase containing Si is only slightly improved, and from the viewpoint of machinability, the amount of the α-phase is also limited. However, even if it is composed of a β1-phase with excellent cutting performance and an α-phase with slightly poor machinability, during cutting, the α-phase acts as a buffer material, or during cutting, it also acts as a stress concentration source at the boundary with the hard β1-phase. Even if the α-phase accounts for up to 75% by mass, the cutting resistance of the alloy is maintained at a low level and the chips are segmented. In addition, since the α-phase acts as a buffer material during cutting or as a stress concentration source at the boundary with the hard β1-phase, the α-phase is preferably in a fine granular shape.

[0171] As described above, through in-depth research on the modification of the β-phase, the dezincification corrosion resistance, stress corrosion cracking resistance, machinability, and mechanical properties of the alloy, it is found that the amount of the α-phase needs to be 20% or more, preferably 30% or more, and more preferably 35% or more. On the other hand, the upper limit of the α-phase is less than 75%, preferably 70% or less, and more preferably 67% or less.

[0172] (γ-phase, structure relationship f5)

[0173] As described in Patent Documents 8 and 10, in a Cu-Zn-Si alloy with a Cu concentration of about 69 to about 80 mass% and a Si concentration of about 2 to about 4 mass%, the γ-phase is a phase contributing to machinability. In Patent Document 15, the γ-phase is necessary in a Pb-free Cu-Zn-Si alloy. Further, in Patent Documents 2 to 6, the β-phase containing Si has good machinability, and the γ-phase containing Si also has good machinability.

[0174] In this embodiment, since the γ-phase hinders the machinability of the alloy, in the following structure and composition relationship f6, a negative coefficient larger than the coefficient of the amount of the β1-phase is given. Further, the γ-phase impairs the ductility and deteriorates the dezincification corrosion resistance. The reason is that in this embodiment, the γ-phase cannot be modified. In a Cu-Zn-Si alloy, the appearance of the γ-phase sometimes cannot be avoided, but at least it needs to be restricted. That is, the proportion (area ratio) of the γ-phase is made less than 4%, preferably less than 2%, more preferably less than 1%, and most preferably the γ-phase does not exist, that is, f5 = 0.

[0175] (Structure and composition relationship f6)

[0176] f6 = β1 × ([Si]) 1 / 2-γ × 2 + ([Pb] + [Bi]) 1 / 2 × 20 + ([P]) 1 / 2 × 15

[0177] The structure and composition relational expression f6 is a simple conditional expression for obtaining good machinability of the alloy. In f6, the amount of the β1 phase, the amount of Si contained in the alloy within the composition range of the present application, the amounts of Pb and Bi, and the amount of P are treated as having a positive effect, while the amount of the γ phase is treated as having a negative effect. That is, f6 is obtained by adding the amount obtained by multiplying the amount of the β1 phase containing Si and P by the 1 / 2 power of the amount of Si, the amount obtained by multiplying the 1 / 2 power of the sum of the amounts of Pb and Bi by the coefficient 20, and the amount obtained by multiplying the 1 / 2 power of the amount of P by the coefficient 15, and subtracting the amount obtained by multiplying the amount of the γ phase by the coefficient 2 from their total. The properties of the β1 phase (modified β phase) are directly affected by the Si concentration and also by the P concentration, and if a very small amount of Pb or Bi is contained, the machinability will be improved. On the other hand, in the present application, the γ phase hinders the machinability. It has been found that there is a profound relationship between the degree of improvement in the machinability of Pb or Bi and the 1 / 2 power of the amounts of Pb and Bi. Both Pb and Bi exhibit significant effects even in very small contents, and as the content increases, the improvement effect on the machinability increases, but the increase rate gradually slows down. In the alloy composed of the β1 phase (modified β phase), a very small amount of Pb or Bi exhibits a significant effect on the machinability, and this effect cannot be obtained from the relationship between the amount of Pb and the machinability of the conventional Cu-Zn-Pb alloy.

[0178] Through in-depth research, it has been found that in order to obtain good machinability, f6 is more than 27, preferably 33 or more, more preferably more than 35, and further preferably 38 or more, approaching the machinability of the free-cutting brass rod added with 3 mass% of Pb.

[0179] Here, Figures 1A to 6B presents the metallographic structure photos of various alloys and the photos of the dezincification corrosion test results of ISO 6509.

[0180] Figure 1AIt is a micrograph of the structure of the copper alloy in the embodiment. The copper alloy is obtained by subjecting Alloy No. S01 to Process No. A2. Specifically, Alloy No. S01 has a composition of Zn - 63.3 mass% Cu - 0.95 mass% Si - 0.069 mass% P - 0.063 mass% Pb - 0.017 mass% Bi. In Process No. A2, hot extrusion is carried out at 630 °C, and cooling treatment is started at 580 °C, such that both the average cooling rate in the temperature range from 580 °C to 300 °C and the average cooling rate in the temperature range from 500 °C to 300 °C are 1020 °C / min. Additionally, the average cooling rate in the temperature range from the cooling treatment start temperature of 580 °C to 500 °C can be easily calculated based on the average cooling rate in the temperature range from 580 °C to 300 °C and the average cooling rate in the temperature range from 500 °C to 300 °C.

[0181] Figure 1B is the result of a dezincification corrosion test conducted on the Figure 1A alloy according to the test method of ISO 6509, and it is a cross-sectional metallographic structure photograph including the part showing the maximum corrosion depth.

[0182] Figure 2A It is a micrograph of the structure of the copper alloy in the embodiment. The copper alloy is obtained by subjecting Alloy No. S11 to Process No. E2. Specifically, Alloy No. S11 has a composition of Zn - 62.5 mass% Cu - 0.96 mass% Si - 0.064 mass% P - 0.072 mass% Pb. In Process No. E2, hot extrusion is carried out at 550 °C, such that the average cooling rate in the temperature range from 500 °C to 300 °C is 20 °C / min, and a bar with a diameter of 50 mm and a length of 200 mm is obtained. The bar is heated, placed horizontally, and hot forged at 680 °C to make the thickness 20 mm, and cooling treatment is started at 565 °C, such that both the average cooling rate in the temperature range from 565 °C to 300 °C and the average cooling rate in the temperature range from 500 °C to 300 °C are 900 °C / min.

[0183] Figure 2B is the result of a dezincification corrosion test conducted on the Figure 2A alloy according to the test method of ISO 6509, and it is a cross-sectional metallographic structure photograph including the part showing the maximum corrosion depth.

[0184] Figure 3AIt is a microstructural observation photograph of the copper alloy in the embodiment. The copper alloy is obtained by performing Process No. E13H on Alloy No. S11. Specifically, Alloy No. S11 has a composition of Zn - 62.5 mass% Cu - 0.96 mass% Si - 0.064 mass% P - 0.072 mass% Pb. In Process No. E13H, hot extrusion is performed at 550 °C, and the average cooling rate in the temperature range from 500 °C to 300 °C is 20 °C / min to obtain a bar with a diameter of 50 mm and a length of 200 mm. The bar is heated, placed horizontally, and hot forged at 630 °C to make the thickness 20 mm, and then cooled at an average cooling rate of 35 °C / min. Subsequently, the cooling treatment is started at 455 °C, and the average cooling rate in the temperature range from 455 °C to 300 °C is 800 °C / min. Figure 3A The alloy of Figure 2A has a different cooling treatment start temperature from the alloy of

[0185] Figure 3B This is the result of a dezincification corrosion test performed on the alloy of Figure 3A according to the test method of ISO 6509, and it is a cross-sectional metallographic structure photograph including the part showing the maximum corrosion depth.

[0186] Figure 4A It is a microstructural observation photograph of the copper alloy in the embodiment. The copper alloy is obtained by performing Process No. E6 on Alloy No. S43. Specifically, Alloy No. S43 has a composition of Zn - 63.3 mass% Cu - 0.98 mass% Si - 0.084 mass% P - 0.060 mass% Pb - 0.28 mass% Sn. In Process No. E6, the casting cast into a mold die with a diameter of 55 mm is machined to a diameter of 50 mm and cut to a length of 200 mm. The casting is heated, placed horizontally, and hot forged at 630 °C to make the thickness 20 mm, and the cooling treatment is started at 565 °C, and both the average cooling rate in the temperature range from 565 °C to 300 °C and the average cooling rate in the temperature range from 500 °C to 300 °C are 900 °C / min.

[0187] Figure 4B This is the result of a dezincification corrosion test performed on the alloy of Figure 4A according to the test method of ISO 6509, and it is a cross-sectional metallographic structure photograph including the part showing the maximum corrosion depth.

[0188] Figure 5AIt is a micrograph of the structure of the copper alloy in the embodiment. The copper alloy is obtained by subjecting Alloy No. S02 to Process No. A34H and Process No. G1. Specifically, Alloy No. S02 has a composition of Zn - 62.9 mass%, Cu - 0.98 mass%, Si - 0.071 mass%, P - 0.071 mass%, and P. In Process No. A34H, hot extrusion is performed at 615°C, and the average cooling rate from 500°C to 300°C is 18°C / min to obtain the alloy. In Process No. G1, the alloy is further heated at 580°C for 30 minutes, and cooling treatment is started from 560°C, so that both the average cooling rate in the temperature range from 560°C to 300°C and the average cooling rate in the temperature range from 500°C to 300°C are 1800°C / min.

[0189] Figure 5B is the result of a dezincification corrosion test on the Figure 5A alloy according to the test method of ISO 6509, and it is a cross-sectional metallographic structure photograph including the part showing the maximum corrosion depth.

[0190] Figure 6A It is a micrograph of the structure of the copper alloy in the embodiment. The copper alloy is obtained by subjecting Alloy No. S02 to Process No. E14H. Specifically, Alloy No. S02 has a composition of Zn - 62.9 mass%, Cu - 0.98 mass%, Si - 0.071 mass%, P - 0.071 mass%, and Pb. In Process No. E14H, hot extrusion is performed at 550°C, and the average cooling rate from 500°C to 300°C is 20°C / min to obtain a bar with a diameter of 50 mm and a length of 200 mm. The bar is heated, placed horizontally, and hot forged at 630°C to make the thickness 20 mm, and then naturally cooled. The average cooling rate in the temperature range from 500°C to 300°C is 25°C / min.

[0191] Figure 6B is the result of a dezincification corrosion test on the Figure 6A alloy according to the test method of ISO 6509, and it is a cross-sectional metallographic structure photograph including the part showing the maximum corrosion depth.

[0192] As Figure 1A , Figure 2A , Figure 4A , Figure 5A shown, for hot extrusions, hot forgings, hot forgings where the billet is a casting, and extrusions obtained by performing additional heat treatment on hot extrusions, in metallographic microscope photographs, grain boundaries, which are patterns of grain boundaries, are observed in the β1 phase together with the α-phase grain boundaries. Here, the grain boundary refers to the linear pattern observed in the β1 phase and penetrating through the β1-phase grains as Figure 1A shown.

[0193] As shown by these, grain boundaries were identified within the modified β-phase, i.e., the β1-phase. On the other hand, in Figure 3A , slight black streak-like substances were observed within the β-phase, but no grain boundaries penetrating the β-phase grains were seen. In Figure 6A , no signs of grain boundaries were seen within the β-phase at all. Instead, in Figure 3A , Figure 6A , granular precipitates about 0.5 to 3 μm in size and colored black were mainly present within the β-phase and at the phase boundary between the β-phase and the α-phase. The granular precipitates were mainly P compounds, but also included Pb particles, mixed particles of Pb and Bi, compounds, oxides, and sulfides of Fe, etc., which could be distinguished by microscopic observation, but were slightly difficult to distinguish in the printed photographs. Precipitates within the α-phase that deviated from the size of the said precipitates were not P compounds. In Figure 3A , Figure 6A , within the field of view of the printed photograph, there were mainly about 1000 P compounds. In Figure 1A , Figure 2A , Figure 4A , Figure 5A , fine granular P compounds, etc. were either absent or present in small amounts, at least 1 / 10 or 1 / 50 less than the number of precipitates in Figure 3A , Figure 6A . Thus, whether grain boundaries exist within the β1-phase or the β-phase depends on whether the cooling treatment start temperature is higher or lower than about 500 °C, and whether a large amount of P compounds are present depends on whether the cooling treatment start temperature is higher or lower than about 500 °C.

[0194] Then, the results after the dezincification corrosion test of ISO 6509 on these alloys are shown in Figure 1B , Figure 2B , Figure 3B , Figure 4B , Figure 5B , Figure 6B . For the specimens where grain boundaries were observed within the β1-phase ( Figure 1A , Figure 2A , Figure 4A , Figure 5A ), the maximum corrosion depth was 120 μm or less, but for the specimens where no grain boundaries were observed within the β-phase, the maximum corrosion depths were 350 μm ( Figure 3A ), 460 μm ( Figure 6A ), showing a corrosion depth difference of 3 to 5 times. In particular, the corrosion depth of the specimen containing 0.28 mass% of Sn was good, being 40 μm ( Figure 4A ). In addition, the morphology of the dezincification corrosion was selective corrosion of the β1-phase and the β-phase. Even for the β1-phase and the β-phase, these phases were preferentially dezincified, but compared with the β-phase, the progress of dezincification corrosion in the β1-phase could be delayed to about 1 / 3 or less.

[0195] <Properties>

[0196] (Normal temperature strength and high temperature properties)

[0197] For components and parts such as water supply related appliances, pipe fittings, automobiles, and electrical parts which are the usage objects of this embodiment, thinning and weight reduction are strongly required. As the required strength, tensile strength is emphasized, and the balance between strength and ductility is also important.

[0198] Therefore, hot extruded parts, hot rolled parts, and hot forged parts are preferably high strength workpieces with a tensile strength of 460 N / mm 2 or more in the state where hot working is completed without performing cold working.

[0199] The tensile strength is more preferably 490 N / mm 2 or more, and further preferably 520 N / mm 2 or more. Most of the parts used in valves, joints, pressure vessels, air conditioners, and refrigerators are made by hot extruded parts and hot forging. The tensile strength of the currently used Pb - added copper alloy C3604 is about 390 - 420 N / mm 2 , and the elongation is about 30 - 35%, so weight reduction is achieved by increasing strength.

[0200] On the other hand, sometimes light sizing or cold working such as bending is performed on machined parts, and it is required not to crack. Machinability requires the material to have a certain brittleness to break the chips, but cold workability is the opposite characteristic. Similarly, tensile strength and ductility are opposite characteristics, and it is ideal to achieve a high balance between tensile strength and ductility (elongation). That is, at least the tensile strength is 450 N / mm 2 or more, the elongation is 10% or more, and the product of the tensile strength (S) and the square root of {(elongation (E%) + 100) / 100}, that is, f7 = S × √{(E + 100) / 100} 1 / 2 is preferably 540 or more, which is a measure of a high strength and high ductility material. f7 is more preferably 570 or more, and further preferably 600 or more. When cold working with a cold work rate of 3 - 15% is included, an elongation of 10% or more and a tensile strength of 520 N / mm 2 or more can be achieved at the same time. Incidentally, when it is the aforementioned Pb - added copper alloy, f7 is about 470.

[0201] (Electrical conductivity)

[0202] In the applications of the present embodiment, it includes parts of electrical and electronic equipment, automotive parts in the development of electric vehicles (EVs), and other highly conductive components and parts. Currently, in these applications, phosphor bronze (Japanese JIS standards, C5191, C5210) containing Sn in an amount of 6% by mass or 8% by mass is more commonly used, and their conductivity is approximately 14% IACS and 12% IACS respectively. Therefore, if the conductivity of the copper alloy of the present embodiment is 15% IACS or more, there will be no problem with electrical conductivity. In addition, there is no particular limitation on the upper limit of the conductivity because when the conductivity becomes better, there are almost no problems in actual use.

[0203] (Hot workability)

[0204] The free-cutting copper alloy of the present embodiment is characterized in that it has excellent deformation ability at 540 - 750 °C, can be hot-extruded into a rod with a smaller cross-sectional area, and can be hot-forged into a complex shape. Due to the good energy condition and the shape (granular) of the α-phase, the hot working temperature is preferably less than 750 °C, more preferably less than 720 °C, and from the perspective of hot deformation resistance, it is preferably more than 540 °C, more preferably more than 560 °C.

[0205] <Manufacturing process>

[0206] Next, the manufacturing method of the free-cutting copper alloy of the embodiment of the present invention will be described.

[0207] The metallographic structure of the alloy of the present embodiment changes not only according to the composition but also according to the manufacturing process. It is affected not only by the hot working temperature and heat treatment conditions of hot extrusion and hot forging, but also by the average cooling rate during the cooling process of hot working or heat treatment. Through in-depth research, it is found that during the cooling process of hot working or heat treatment, the cooling treatment start temperature, the average cooling rate in the temperature range from the cooling treatment start temperature to 500 °C, and the average cooling rate in the temperature range from 500 °C to 300 °C have a greater impact on the metallographic structure.

[0208] (Melting and casting)

[0209] Melting is carried out at a temperature about 100 - about 300 °C higher than the melting point (liquidus temperature) of the alloy of the present embodiment, that is, about 950 - about 1200. The molten metal at a temperature about 50 - about 200 °C higher than the melting point, that is, about 900 - about 1100 °C, is poured into a specific mold and cooled by several cooling methods such as air cooling, slow cooling, and water cooling. Then, after solidification, various changes occur in the constituent phases.

[0210] (Hot working)

[0211] Examples of hot working processes include hot extrusion, hot forging, and hot rolling. When two or more hot working processes are carried out, the final hot working process is carried out under the following conditions.

[0212] First, regarding hot extrusion, as a preferred embodiment, although it also depends on the extrusion ratio (hot working rate) and equipment capacity, in practice, hot extrusion is carried out at a temperature where the material temperature (extrusion temperature) immediately after hot working exceeds 540°C and is lower than 750°C. The extruded rod is coiled into a coil shape, or when the cross-sectional area of the extruded rod is large, it is extruded while maintaining a straight rod state on the workbench. The lower limit of the hot extrusion temperature is related to the deformation resistance in the hot state. When the extrusion temperature is low, the α-phase grains are granular and fine, and the dezincification corrosion resistance, stress corrosion cracking resistance, and machinability are good. However, when the extrusion ratio is large, considering the relationship between the equipment capacity and the starting temperature of the following cooling treatment, the extrusion temperature is preferably 560°C or higher. The upper limit is related to the shape of the α-phase. By controlling within a narrower temperature range, a stable metallographic structure can be obtained. If hot extrusion is carried out at a temperature of 750°C or higher, the metallographic structure once becomes β single-phase or the proportion of the β-phase is 90% or more, so that the shape of the α-phase grains easily becomes needle-like, or coarse α-phase grains are likely to appear. If needle-like and coarse α-phase grains appear, the strength is slightly reduced, resulting in a slightly worse balance between strength and ductility. The large and coarse α-phase grains with long sides become obstacles to cutting, resulting in poor machinability. Furthermore, the dezincification corrosion resistance and stress corrosion cracking resistance also deteriorate. The extrusion temperature is preferably 720°C or lower. The shape of the α-phase grains is related to the composition relationship formula f1. When the composition relationship formula f1 is 59.0 or less, the extrusion temperature is preferably lower than 720°C. Compared with copper alloys containing Pb, extrusion is carried out at a lower temperature, thereby achieving better machinability and strength.

[0213] Then, by designing the cooling conditions after hot extrusion, modification of the β-phase can be carried out, thereby obtaining a material with better machinability and good dezincification corrosion resistance and stress corrosion cracking resistance. That is, during the cooling process after hot extrusion, first, the cooling treatment is started at a temperature lower than 670°C and higher than 500°C, and then, the average cooling rate in the temperature range from the start temperature of the cooling treatment to 500°C and the average cooling rate in the temperature range from 500°C to 300°C are set to be at least more than 300°C / minute, preferably more than 600°C / minute, and more preferably 900°C / minute or more for cooling. Here, as a general implementation method, if a conventional cooling method is used, the average cooling rate in the temperature range from the start temperature of the cooling treatment to 500°C and the average cooling rate in the temperature range from 500°C to 300°C are roughly the same, or in some cases, the former is slightly faster. If cooling is further carried out at a more preferred cooling rate, the β1-phase is more modified. If the β1-phase is more modified, a material with better machinability and good dezincification corrosion resistance and stress corrosion cracking resistance can be obtained. There is no particular limitation on the upper limit of the average cooling rate in the temperature range from the start temperature of the cooling treatment to 500°C and the temperature range from 500°C to 300°C, as long as it is a cooling rate achievable in ordinary production equipment. If it must be mentioned, the cooling rate is preferably about 9000°C / minute or less. By cooling at an average cooling rate exceeding 300°C / minute to carry out the modification of the β-phase and etching with a mixed solution of hydrogen peroxide and ammonia water, when observing the metallographic structure with a metallographic microscope at a magnification of 500 times, grain boundaries can be observed in the modified β-phase. In addition, when the average cooling rate in the temperature range from the start temperature of the cooling treatment to 500°C and the average cooling rate in the temperature range from 500°C to 300°C are 300°C / minute or less, grain boundaries cannot be observed in the β-phase. The faster the cooling rate, the greater the degree of modification to the modified β-phase, that is, the β1-phase. When cooling from a temperature lower than 300°C to room temperature, as it approaches room temperature, the cooling rate slightly slows down, but it is more ideal to continue the cooling in the temperature range from 500°C to 300°C.

[0214] On the other hand, the start temperature of the cooling treatment also affects the modification of the β-phase. It is preferably started at a temperature higher than 530°C, and more preferably at a temperature higher than 550°C. When the cooling treatment is started at a temperature lower than 550°C, if the cooling rate from 550°C to the start temperature of the cooling treatment is slow, compounds of P and Zn or P, Zn, and Si start to form, and the formation of P compounds is further promoted below 530°C. When the cooling rate exceeds 300°C / minute, almost no P compounds are formed, but if the start temperature of the cooling treatment is lower than 550°C, P compounds are observed in the metallographic structure.

[0215] However, if the starting temperature of the cooling treatment is above 670 °C, the proportion of the β1 phase is too large, resulting in poor ductility, dezincification corrosion resistance, and stress corrosion cracking resistance of the alloy. Therefore, the starting temperature of the cooling treatment needs to be lower than 670 °C, preferably lower than 650 °C.

[0216] In view of the measurable measurement positions, the hot working temperature is defined as the temperature of the hot worked piece that can be measured approximately 2 seconds or 3 seconds after the end of hot extrusion, hot forging, or hot rolling. The metallographic structure is affected by the temperature after processing that has just undergone large plastic deformation.

[0217] Next, hot forging will be described. Hot forging mainly uses hot extruded parts as blanks, but continuous casting rods can also be used. Since the forging blank does not undergo final hot working, cooling measures are not required. Compared with hot extrusion, hot forging has a faster processing speed and can be processed into complex shapes. In some cases, it is strongly processed into a wall thickness of about 3 mm. Moreover, the weight of a single forging is from several tens of grams to several kilograms. Smaller forgings are rapidly cooled during forging, and the subsequent cooling rate is also relatively fast. Therefore, the heating temperature of the blank during forging is higher than the heating temperature of the ingot during hot extrusion. As a preferred embodiment, the temperature of the hot forged product, that is, the material temperature approximately 2 seconds or 3 seconds after forging, exceeds 540 °C and is preferably lower than 750 °C.

[0218] Hot forging is also related to the composition relationship formula f1. When the composition relationship formula f1 is 59.0 or less, the hot forging temperature is preferably lower than 720 °C. Although it also depends on the hot forging processing rate, the lower the temperature, the smaller the crystal grain size of the α phase, the shape of the α phase grains changes from needle-like to granular, the strength increases, the balance between strength and ductility is better, and the machinability, dezincification corrosion resistance, and stress corrosion cracking resistance are better.

[0219] Also, similar to hot extrusion, by designing the cooling rate after hot forging, a material with good dezincification corrosion resistance, stress corrosion cracking resistance, and good machinability can be obtained. That is, during the cooling process after hot forging, first, the cooling treatment is started at a temperature below 670°C and above 500°C, and then, the average cooling rate in the temperature range from the start temperature of the cooling treatment to 500°C and the average cooling rate in the temperature range from 500°C to 300°C are set to be at least more than 300°C / min, preferably more than 600°C / min, and more preferably 900°C / min or more for cooling. Here, as a general implementation method, if a conventional cooling method is used, the average cooling rate in the temperature range from the start temperature of the cooling treatment to 500°C is roughly the same as or slightly faster than the average cooling rate in the temperature range from 500°C to 300°C. By making the average cooling rate exceed 300°C / min, the modification of the β phase is carried out, and etching is performed using a mixed solution of hydrogen peroxide and ammonia water. When observing the metallographic structure with a metallographic microscope at a magnification of 500 times, grain boundaries can be observed within the modified β phase. In addition, when the average cooling rate in the temperature range from 500°C to 300°C is 300°C / min or less, grain boundaries cannot be observed within the β phase. The faster the cooling rate, the greater the degree of modification to the modified β phase, i.e., the β1 phase. Similar to hot extrusion, when cooling from a temperature below 300°C to room temperature, as it approaches room temperature, the cooling rate slightly slows down, but it is more ideal to continue the cooling in the temperature range from 500°C to 300°C. There is no particular limitation on the upper limit of the average cooling rate in the temperature range from the start temperature of the cooling treatment to 500°C and the temperature range from 500°C to 300°C. If it has to be mentioned, the cooling rate is preferably about 9000°C / min or less.

[0220] On the other hand, the start temperature of the cooling treatment also affects the modification of the β phase. It is preferably started at a temperature above 530°C, more preferably at a temperature above 550°C. When the cooling treatment is started at a temperature below 550°C, if the cooling rate from 550°C to the start temperature of the cooling treatment is slow, compounds of P and Zn or P, Zn, and Si will start to form, and the formation of P compounds will be further promoted below 530°C. When the cooling rate exceeds 300°C / min, almost no P compounds will form, but if the start temperature of the cooling treatment is below 550°C, P compounds will be observed in the metallographic structure. On the other hand, if the start temperature of the cooling treatment is 670°C or higher, the proportion of the β1 phase is too large, resulting in poor ductility, dezincification corrosion resistance, and stress corrosion cracking resistance of the alloy. Therefore, the start temperature of the cooling treatment needs to be below 670°C, preferably below 650°C. In addition, after hot forging, it is placed in a simple furnace with an atmosphere temperature set to about 550 - about 600°C for dozens of seconds to several minutes, and then the cooling treatment is started, so that a more uniform and stable forged product can be obtained.

[0221] Further, in order to improve stress corrosion cracking resistance, shot peening is an effective method after the aforementioned hot forging-cooling treatment. Other copper alloys also improve stress corrosion cracking resistance by applying compressive stress to the surface, such as shot peening, etc. However, when it comes to the alloy of the present application containing β1 phase, the effect of shot peening is greater.

[0222] During hot rolling, the ingot is heated and rolled repeatedly 5 to 15 times. And, the material temperature at the end of the final hot rolling (the material temperature after 2 to 3 seconds from the end time) is preferably over 540 °C and below 750 °C, more preferably below 670 °C. After hot rolling, the rolled piece is cooled. Similarly to hot extrusion, the cooling treatment is started at a temperature higher than 500 °C and lower than 670 °C, and the average cooling rate in the temperature range from the cooling treatment start temperature to 500 °C and the average cooling rate in the temperature range from 500 °C to 300 °C are set to be at least over 300 °C / minute, preferably over 600 °C / minute, and further preferably 900 °C / minute or more for cooling. When cooling from a temperature below 300 °C to room temperature, as it approaches room temperature, the cooling rate slightly slows down, but it is more ideal to continue the cooling in the temperature range from 500 °C to 300 °C. There is no particular limitation on the upper limit of the average cooling rate in the temperature range from the cooling treatment start temperature to 500 °C and the temperature range from 500 °C to 300 °C. If forced to mention, the cooling rate is preferably about 9000 °C / minute or less.

[0223] (Heat treatment)

[0224] In this application, when it is impossible to start the cooling treatment at a temperature higher than 500 °C after the aforementioned final hot working, or when it is impossible to cool in such a way that the average cooling rate in the temperature range of 500 °C to 300 °C exceeds 300 °C / minute, the modification of the β phase cannot be carried out. Also, when making small-diameter rods, wires, etc., in the case of processes including cold working and annealing with heat application, etc., the β phase is basically not modified. In these cases, annealing is carried out under the condition of holding at a temperature exceeding 520 °C and lower than 630 °C for 1 minute to 5 hours. In the cooling after annealing, the cooling treatment starts at a temperature higher than 500 °C, and the β phase is modified by cooling in such a way that the average cooling rate in the temperature range from the cooling treatment start temperature to 500 °C exceeds 300 °C / minute and the average cooling rate in the temperature range of 500 °C to 300 °C exceeds 300 °C / minute, thereby forming the β1 phase. Regarding the annealing conditions, when there are multiple annealing processes, only the last annealing is required. From the perspective of the formation temperature of the P compound, the annealing temperature is preferably 530 °C or higher, more preferably 550 °C or higher. Also, according to the modification degree of the β1 phase, the average cooling rate in the temperature range of 500 °C to 300 °C is set to preferably exceed 600 °C / minute, more preferably 900 °C / minute or higher. As described above, this heat treatment is applicable to hot-worked parts that cannot be cooled under specific conditions after hot working and materials that are annealed more than once after cold working is performed on the materials after hot working, etc.

[0225] There is no particular limitation on the upper limit of the average cooling rate in the temperature range from the cooling treatment start temperature to 500 °C and in the temperature range of 500 °C to 300 °C. If it has to be mentioned, the cooling rate is preferably about 9000 °C / minute or lower.

[0226] (Cold working process)

[0227] When it comes to hot-extruded rods, in order to obtain high strength and good dimensional accuracy, or in order to make the extruded rods and coils into a straight shape with less bending, cold working is sometimes carried out on the hot-extruded parts. For example, the hot-extruded parts are cold drawn at a processing rate of about 2 to about 30%, and according to the situation, drawing is carried out, and then straightening is carried out.

[0228] Cold working and annealing are repeatedly carried out on slender rods, wires or rolled parts, and after the aforementioned final heat treatment, cold working and straightening with a final processing rate of 0 to about 30% are carried out. The closer the final processing rate is to 0%, the more difficult it is for the processed parts to crack when mild cold working such as caulking or bending is carried out on the processed parts.

[0229] (Low-temperature annealing)

[0230] In bars, wires, forgings, and rolled products, sometimes in the final process, the bars, wires, forgings, and rolled products are subjected to low-temperature annealing at a temperature below the recrystallization temperature. The main purposes are to remove residual stress, correct the straightness of the bars (linearity of the bars), and adjust and improve the metallographic structure. However, if heat is applied to the alloy, the modification of the β1 phase obtained by hot working processes and heat treatment modification will be damaged. For example, if heated at 300 °C for 2 hours, the modification of the β phase is damaged, returning from the modified β1 phase to the original β phase, and the improved machinability, dezincification corrosion resistance, and stress corrosion cracking resistance become the characteristics of the alloy composed of the original β phase. Therefore, although low-temperature annealing is not recommended, temperatures below about 150 °C are acceptable.

[0231] According to the free-cutting alloy according to an embodiment of the present invention having the above configuration, since the alloy composition, composition relationship formula, metallographic structure, structure relationship formula, structure and composition relationship formula are defined in the above manner, excellent machinability can be obtained even with a small Pb content, and it has good dezincification corrosion resistance, stress corrosion cracking resistance, excellent hot workability, high strength, and excellent balance between strength and ductility.

[0232] The embodiments of the present invention have been described above, but the present invention is not limited thereto, and can be appropriately changed within the scope not departing from the technical requirements of the present invention.

[0233] Examples

[0234] The results of the confirmation experiments conducted to confirm the effects of the present embodiment are shown below. In addition, the following examples are used to illustrate the effects of the present embodiment, and the constituent elements, processes, and conditions described in the examples do not limit the technical scope of the present embodiment.

[0235] A trial production test of a copper alloy was carried out using a low-frequency melting furnace and a semi-continuous casting machine used in actual operation.

[0236] In addition, a trial production test of a copper alloy was carried out using laboratory equipment.

[0237] The alloy compositions are shown in Tables 5 to 7. And the manufacturing processes are shown in Tables 8 to 17. In addition, in the composition, "Mm" represents misch metal, indicating the total amount of rare earth elements. Each manufacturing process is shown below. In Tables 8 to 12 and Tables 14 to 16, the cooling rate of hot working such as hot extrusion, hot forging, or hot compression refers to the average cooling rate from the end of hot working to the start of the cooling treatment.

[0238]

[0239]

[0240]

[0241] [Table 8]

[0242] Actual machine manufacturing process AA: bar (indirect extrusion)

[0243]

[0244] [Table 9]

[0245] Actual machine manufacturing process AB: bar (indirect extrusion)

[0246]

[0247] [Table 10]

[0248] Actual machine manufacturing process AD: bar (indirect extrusion)

[0249]

[0250] [Table 11]

[0251] Actual machine manufacturing process AC: bar (direct extrusion)

[0252]

[0253] [Table 12]

[0254] Laboratory extrusion process B

[0255]

[0256] [Table 13]

[0257] Laboratory casting, process C

[0258]

[0259] [Table 14]

[0260] Actual machine hot forging process D: flared nut

[0261]

[0262] [Table 15]

[0263] Actual machine hot forging process E: upset forging

[0264]

[0265] [Table 16]

[0266] Laboratory hot compression process F

[0267]

[0268] [Table 17]

[0269] Heat treatment process G

[0270]

[0271] Actual machine manufacturing processes AA, AB, AD

[0272] (Process Nos. A1 to A5, A11H to A14H, A21 to A25, A31H to A34H, A41 to A44, A46H, A47H)

[0273] Manufacture a billet with a diameter of 240 mm using an actual low-frequency melting furnace and a semi-continuous casting machine. Use raw materials that conform to actual operations. Cut the billet into lengths of 800 mm and heat it. Extrude a round bar with a diameter of 20.9 mm using an indirect extrusion press with a rated capacity of 2,750 tons. The extruded part (round bar) is wound into a coil shape in a groove located slightly away from the extrusion press. The groove can perform water cooling with adjustable water volume. When the extruded part reaches a specific temperature in the groove, start the cooling process (water cooling) while adjusting the water volume. Additionally, sometimes start the cooling process while placing the extruded part in the groove. Temperature measurement is carried out using a radiation thermometer. When extruding using the extrusion press, start the cooling process. At this time, measure the temperature of the extruded part until it reaches 500 °C and 300 °C. Additionally, in subsequent temperature measurements during hot extrusion and hot forging, simultaneously use a radiation thermometer of model IGA8Pro / MB20 manufactured by LumaSense Technologies Inc and a contact thermometer.

[0274] In Process AA, namely Processes No. A1 to A5, A11H to A14H, the extrusion temperature is 630°C. In Process AB, namely Processes No. A21 to A25, A31H to A34H, the extrusion temperature is 615°C. In Process No. AD, namely Processes No. A41 to A44, A46H, A47H, the extrusion temperature is 720°C. And, after the extruded part with a diameter of 20.9 mm coiled into a coil shape reaches a specific temperature in the groove, the cooling process starts, and the time when the extruded part reaches 500°C and 300°C is measured. Although the temperature below 300°C cannot be accurately measured by a radiation thermometer, the cooling continues under the original cooling conditions until the material is cooled to a temperature below about 100°C. Regarding the detailed conditions, as shown in Tables 8, 9, and 10, in Processes No. A1 to A5, A11H to A14H, Processes No. A21 to A25, A31H to A34H, and Processes No. A41 to A44, A46H, A47H, the average cooling rate from after extrusion to the start of the cooling process, the start temperature of the cooling process, the average cooling rate in the temperature range from the start temperature of the cooling process to 300°C, and the average cooling rate in the temperature range from 500°C to 300°C may sometimes be different. When the start temperature of the cooling process is lower than 500°C, the average cooling rate in the temperature range from the start temperature of the cooling process to 300°C is regarded as the cooling rate in the temperature range from 500°C to 300°C. In addition, the average cooling rate in the temperature range from the start temperature of the cooling process to 500°C can be easily calculated based on the average cooling rate in the temperature range from the start temperature of the cooling process to 300°C and the average cooling rate in the temperature range from 500°C to 300°C. Therefore, it can be confirmed that the cooling rate in the temperature range from the start temperature of the cooling process to 500°C is the same as the cooling rate in the temperature range from 500°C to 300°C, or the cooling is slightly faster under some conditions. After the cooling is completed after hot extrusion, the extruded part is placed on a combined drawing machine with a processing rate of 8.4% and drawn and straightened into a straight bar with a diameter of φ20 mm.

[0275] In Process No. A25 and Process No. A31H, the bar obtained in Process No. A21 is used, and further, in the laboratory, low-temperature annealing is carried out at 130°C for 5 hours and at 300°C for 2 hours. These Process AA parts, Process AB parts, and Process AD parts are used for microscopic observation, cutting tests, dezincification corrosion tests, and tensile tests.

[0276] Process AC, bar with a diameter of φ50 mm

[0277] (Process No. A50)

[0278] As a trial production part for forging, prepare a φ50 mm bar (Process No. A50) according to Process AC shown in Table 11. Use an actual low-frequency melting furnace and a semi-continuous casting machine to manufacture a billet with a diameter of 240 mm, and cut the billet into a length of 800 mm. Using this billet, extrude the billet into a round bar with a diameter of 50 mm at 550 °C using a direct extrusion press with a rated capacity of 3000 tons. Place the extruded straight bar on a steel workbench and perform natural cooling until it reaches room temperature. Then, perform straightening and provide it as a billet for the following upset forging. Since it is provided as a billet for hot forging, which is the final hot working process, no special cooling treatment is performed, and the average cooling rate from 500 °C to 300 °C is 20 °C / minute.

[0279] Laboratory extruded part, Process B

[0280] (Process No. B1, B2, B3H)

[0281] Regarding Process B, as shown in Table 12, in the laboratory, melt the raw materials at a specific composition ratio. Pour the molten metal into a mold with a diameter of 100 mm and a length of 200 mm to produce billets. In addition, in some billets, impurities such as Fe are intentionally added. The concentration of intentionally added impurities such as Fe is at approximately the same level or lower than that of commercially available brass containing Pb.

[0282] Heat these billets. In Process No. B1, set the extrusion temperature to 670 °C and extrude them into round bars with a diameter of 20 mm. After extrusion, start the cooling treatment at 540 °C and cool them at an average cooling rate from 500 °C to 300 °C of 960 °C / minute. It can be confirmed that the average cooling rate from 540 °C to 500 °C is approximately the same as the average cooling rate from 500 °C to 300 °C. Then, continue cooling under the original cooling conditions until the material is cooled to a temperature below about 100 °C. In Process No. B3H, set the extrusion temperature to 670 °C and extrude them into round bars with a diameter of 20 mm. Instead of performing a cooling treatment, cool them at an average cooling rate from 500 °C to 300 °C of 40 °C / minute.

[0283] These Process Nos. B1 and B3H are used for microscopic observation, cutting tests, dezincification corrosion tests, and tensile tests. A part of Process No. B3H is used as a hot forging billet for Process D.

[0284] In Process No. B2, set the extrusion temperature to 590 °C, extrude them into a diameter of 50 mm, do not perform a cooling treatment, and make the average cooling rate from 500 °C to 300 °C 25 °C / minute, and use it as a forging billet.

[0285] Process C, for forging, hot compression billet: casting

[0286] (Process No. C1, C2)

[0287] As castings used as blanks for forging, the following two types of castings are produced: In the laboratory, raw materials are melted at a specific composition ratio, and a casting obtained by pouring molten metal at about 1000 °C into an iron mold with an inner diameter of 35 mm and a depth of 200 mm (Process No. C1); and a casting obtained by pouring it into an iron mold with an inner diameter of 55 mm and a depth of 200 mm (Process No. C2). When the casting is about 700 °C, the casting is taken out of the mold and naturally cooled without performing a cooling treatment.

[0288] As shown in Table 13, the average cooling rate from 500 °C to 300 °C is 35 °C / minute in Process No. C1 and 23 °C / minute in Process C2. For the casting of Process No. C1, it is machined on a lathe to an outer diameter of 20 mm, and for the casting of Process No. C2, it is machined to an outer diameter of 50 mm, and then finish-machined into a forging blank for the following Process D and Process E and a hot compression blank for Process F.

[0289] Flared nut forging

[0290] (Process D)

[0291] In Process D, a φ20 mm actual machine extrusion rod of Process No. A1, A13H, A21, A34H, A47H, a laboratory extrusion rod of Process No. B3H, and a laboratory casting of Process C1 are used as blanks for the flared nut forging. Then, it is cut so that the weight becomes 120 ± 1 g (119 g to 121 g), and using a 500-ton hot forging press, it is formed into a flared nut forging blank with a 27 mm across flats and a 26 mm length in a hexagonal shape.

[0292] As shown in Table 14, the hot forging temperature is 670°C in processes No. D1, D3 to D7, D12H to D14H, 710°C in process No. D2, 740°C in process No. D8, and 770°C in process No. D15H. Also, except for processes No. D15H and D13H, the average cooling rate from after forging to the start of cooling treatment is 100°C / minute, and it is 120°C / minute in process No. D15H. In process No. D13H, no cooling treatment is performed and it is naturally cooled. As shown in Table 14, the start temperature of the cooling treatment is 475 - 695°C. Except for process No. D13H, the average cooling rate in the temperature range from the start temperature of the cooling treatment to 300°C and the average cooling rate in the temperature range from 500°C to 300°C vary between 240°C / minute and 1980°C / minute. In processes No. D1 to D7 and D14H, the average cooling rate in the temperature range from the start temperature of the cooling treatment to 500°C is the same as the average cooling rate in the temperature range from 500°C to 300°C. In D8 and D15H, the former is slightly faster. In process No. D12H, the average cooling rate from the start temperature of the cooling treatment of 475°C to 300°C is regarded as the average cooling rate in the temperature range from 500°C to 300°C.

[0293] In process No. D7, hot forging and cooling treatment are performed under the same conditions as in process No. D5, and a shot process is further performed. As the conditions for shot peening, steel balls with a diameter of 0.6 mm are used and it is carried out for 10 minutes.

[0294] These hot forged products are finish - machined by cutting into a flared nut that conforms to Japanese JIS B 8607 and has an inner diameter of 5 / 8 inches ( = 15.9 mm). The parts of process D are used for microscopic observation, dezincification corrosion test, and stress corrosion cracking test.

[0295] Closed - die forging

[0296] (Process E)

[0297] Process E is a process for laboratory - forged products. As its billets, the actual - machine extrusion rods of process No. A50, the laboratory extrusion rods of process No. B2, and the laboratory castings of process No. C2 are used, and they are each cut to a length of 180 mm. The round bars are placed horizontally and forged into a thickness of 20 mm using a press with a hot forging pressure of 150 tons.

[0298] (Processes No. E1 to E7, E11H to E15H)

[0299] In processes No. E1, E4 to E6, E12H to E15H, the forging temperature is 630 °C; in process No. E2, the forging temperature is 680 °C; in process No. E3, the forging temperature is 700 °C; in process No. E7, the forging temperature is 720 °C; in process No. E11H, the forging temperature is 740 °C. After hot forging, except for process No. E14H, the average cooling rate before the start of the cooling treatment is 35 °C / min. As shown in Table 15, the cooling treatment starts at a temperature between 690 °C and 455 °C, and the average cooling rate from the start temperature of the cooling treatment to 300 °C varies between 900 °C / min and 200 °C / min, and it is cooled to room temperature using the original cooling method. It can be confirmed that in processes No. E1 to E6, E15H, the average cooling rate in the temperature range from the start temperature of the cooling treatment to 500 °C is approximately the same as the average cooling rate in the temperature range from 500 °C to 300 °C. In processes No. E12H, E13H, the average cooling rate in the temperature range from the start temperature of the cooling treatment to 300 °C is recorded as the average cooling rate in the temperature range from 500 °C to 300 °C. In process No. E14H, the cooling treatment is not performed, and it is naturally cooled, and the average cooling rate from 500 °C to 300 °C is 25 °C / min.

[0300] These upset forgings are cut and used for cutting tests, mechanical properties, dezincification corrosion, and microscopic observation tests.

[0301] Hot compression test

[0302] (Process F)

[0303] Using the actual machine hot extrusion bars of process No. A13H, A34H, and A47H, the laboratory hot extrusion bar of process No. B3H, and the casting of process C1 as blanks, they are finish-machined into φ15 mm and 27 mm in height using a lathe. And, as shown in Table 16, using a 10-ton AMSLER type testing machine equipped with a heating furnace, they are hot compressed to a height of 8 mm at 650 °C under the condition of a strain rate of 0.02 / second. In process No. F1 to F3, the hot-compressed specimens are taken out from the heating furnace and cooled at a cooling rate of 50 °C / minute. Then, the cooling treatment is started at 560 °C, and they are cooled in such a way that the average cooling rate in the temperature range from 500 °C to 300 °C is 2100 °C / minute, and the cooling is continued below 300 °C according to the treatment method until they are cooled to room temperature. In process No. F4H, the cooling treatment is started at 560 °C, and they are cooled in such a way that the average cooling rate from the start temperature of the cooling treatment to 300 °C is 200 °C / minute. In process No. F5H, no special cooling treatment is carried out, but they are cooled in such a way that the average cooling rate in the temperature range from 500 °C to 300 °C is 40 °C / minute. The average cooling rate in the temperature range from the start temperature of the cooling treatment (560 °C) to 500 °C is approximately the same as the average cooling rate in the temperature range from 500 °C to 300 °C. These hot-compressed parts are used for microscopic observation and dezincification corrosion test.

[0304] Heat treatment

[0305] (Process G)

[0306] As shown in Table 17, in Process G, the changes in characteristics were studied by performing heat treatment on the bars and forgings obtained in Processes No. A1, A21, A41, A13H, A34H, A47H, D1, and D13H in a laboratory. Annealing was carried out under the condition of maintaining at 580 °C for 30 minutes or 60 minutes. In Processes No. G1, G2, and G3, after annealing, cooling treatment was started at 560 °C, and cooling was performed in such a way that the average cooling rate in the temperature range from the cooling treatment start temperature to 300 °C was 1800 °C / minute. The average cooling rate in the temperature range from the cooling treatment start temperature (560 °C) to 500 °C was approximately the same as the average cooling rate from 500 °C to 300 °C. In Processes No. G11H and G12H, after annealing at 580 °C, the cooling treatment start temperature was set to 470 °C, and cooling was performed in such a way that the average cooling rate from 470 °C to 300 °C was 1500 °C / minute. In Processes No. G13H and G14H, after annealing at 580 °C, instead of performing special cooling treatment, cooling was performed in such a way that the average cooling rate from 500 °C to 300 °C was 25 °C / minute. These heat-treated parts were used for metallographic microscope observation, the bars were used for cutting tests, dezincification corrosion tests, and tensile tests, and the forgings were used for dezincification corrosion tests and stress corrosion cracking tests.

[0307] (Comparative piece)

[0308] As comparative pieces, φ20 mm bars made of free-cutting brass C3604 containing 3 mass% Pb were prepared. Also, φ50 mm and φ20 mm bars made of forging brass C3771 containing 2 mass% Pb were prepared. They were designated as alloys X, Y, and Z respectively, and all commercially available products were used. Hot forging and cooling treatment were performed on alloy Y under the same conditions as in Processes No. E14H and E1. Hot forging and cooling treatment were performed on alloy Z under the same conditions as in Processes No. D13H and D1. Alloy X was used for metallographic microscope observation, cutting tests, dezincification corrosion tests, and tensile tests. Alloy Y was used for metallographic microscope observation, cutting tests, dezincification corrosion tests, and tensile tests. Alloy Z was used for metallographic microscope observation, dezincification corrosion tests, and stress corrosion cracking tests.

[0309] The following items were evaluated for the above test pieces. The evaluation results are shown in Tables 18 to 56.

[0310] The area ratio of the β phase, i.e., the unmodified β phase, was designated as f4A, distinguished from the area ratio f4 of the β1 phase, and recorded in each table. And when f4 = (area ratio of β1) = 0, in the β1 term of the calculation formula for f6, instead of using β1, the value of f4A = (area ratio of β) was used, and the value calculated therefrom was used as the reference value of f6, and marked with an asterisk "*" beside the value for recording.

[0311] (Observation of Metallographic Structure)

[0312] The metallographic structure is observed by the following method, and the area ratio (%) of each phase such as α-phase, β-phase, γ-phase, etc. is measured by image analysis. In addition, the phase in which grain boundaries are observed in the β-phase is designated as the β1-phase and is distinguished from the β-phase. The α'-phase, β'-phase, and γ'-phase are included in the α-phase, β-phase, and γ-phase, respectively. The α-phase is granular, elliptical in shape, and often accompanied by twins. Around this granular and elliptical α-phase, there exist β-phase and β1-phase. Thus, the α-phase, β-phase, and β1-phase are distinguished from each other.

[0313] The bars and forgings of each test piece are cut parallel to the length direction or parallel to the flow direction of the metallographic structure. Then, the surface is mirror-polished (mirror-grinding), and etched using a mixed solution of hydrogen peroxide and ammonia water. During etching, an aqueous solution prepared by mixing 3 mL of 3 vol% hydrogen peroxide solution and 22 mL of 14 vol% ammonia water is used. At room temperature of about 15 to about 25 °C, the ground surface of the metal is immersed in this aqueous solution for about 2 seconds to about 10 seconds. In addition, since the corrosion resistance in the case where the β1-phase exists is improved compared to the case where the β-phase exists, the immersion time for etching needs to be extended to about 5 to 10 seconds.

[0314] Using a metallographic microscope, the metallographic structure is observed at a magnification of 500 times to obtain the proportion of each phase. According to the condition of the metallographic structure, it is observed at 1000 times to confirm the phases and compounds. In the microscope photos of five fields of view, each phase (α-phase, β-phase, β1-phase, γ-phase) is manually smeared using the image processing software "Photoshop CC". Regarding the distinction between the β-phase and the β1-phase, when one or more β grain boundaries are observed in one field of view, all the β-phase in that field of view is smeared as the β1-phase. Then, binarization is performed using the image processing software "WinROOF2013" to obtain the area ratio of each phase. Specifically, for each phase, the average value of the area ratios of five fields of view is obtained, and the average value is used as the area ratio of each phase. Except for compounds containing P and Si, precipitates, oxides, particles of Pb or Bi, sulfides, and crystallizations, the total area ratio of all constituent phases is set to 100%.

[0315] If the β-phase is modified, when observed with a metallographic microscope using this etching solution, a pattern of grain boundaries, i.e., grain boundaries, is observed in the β-phase. In the present application, when grain boundaries are observed in the β-phase, this β-phase is designated as the β1-phase and is distinguished from the normal β-phase. Here, the grain boundary refers to a linear pattern Figure 1A as shown, which is observed within the β1-phase and penetrates through the grains of the β1-phase.

[0316] In the metallographic structure, in addition to phases, there are sometimes compounds and precipitates of P and Si. Under a metallographic microscope with a magnification of 500 times, the compounds of P with Zn or Si exist as black-gray particles of about 0.5 to about 2 μm, mainly in the β phase, β1 phase, and at the phase boundary between the β phase and the α phase. The compounds of Fe, Mn, Cr with P or Si can be regarded as light blue particles of about 1 to about 5 μm. The particles of Pb or Bi and the particles formed by the combination of Pb and Bi exist as fine black particles of less than 2 μm. These compounds etc. can be roughly distinguished in the metallographic microscope.

[0317] In the characteristic evaluation table, when grain boundaries are observed in the β1 phase (β phase) of the metallographic structure, it is recorded as "B" (present), and when no grain boundaries are observed, it is recorded as "D" (absent).

[0318] Regarding the P compound, when the P content is 0.06% by mass and cooling is carried out at an average cooling rate of 15 to 50 °C / min from 500 °C to 300 °C, about 500 to about 1000 P compounds are observed in a field of view with a magnification of 500 times (80 mm × 120 mm when printed). However, in the printed metallographic structure, it is difficult to distinguish P compounds, the compounds of Fe, Mn, Cr with P or Si, and Pb particles, etc. Therefore, when judging the presence or absence of P compounds based on the printed metallographic structure photo, including P compounds and compounds that may be P compounds, when there are less than 50 in the field of view of the photo, it is assumed that P compounds are absent and evaluated as "D" (absent). When there are 50 or more and less than 300, it is considered that P compounds are present but in small amounts and evaluated as "C" (qualified). When there are 300 or more, it is assumed that P compounds are present and evaluated as "B" (present). The presence or absence and quantity of P compounds are one of the indicators for whether appropriate treatment is carried out.

[0319] When the identification of phases, compounds, and precipitates is difficult, a field emission scanning electron microscope (FE-SEM) (JSM-7000F manufactured by JEOL Ltd.) and an attached energy dispersive spectrometer (EDS) are used. Under the conditions of an acceleration voltage of 15 kV and a current value (set value 15), the phases and precipitates are determined by the electron backscattering diffraction pattern (FE-SEM-EBSP) method at a magnification of 500 times or 2000 times.

[0320] (Conductivity)

[0321] The conductivity was measured using a conductivity measuring device (SIGMATEST D2.068) manufactured by FOERSTER JAPAN LIMITED. In addition, in this specification, the terms "electrical conduction" and "electric conductivity" have the same meaning. Also, since there is a strong correlation between thermal conductivity and electrical conductivity, it means that the higher the electric conductivity, the better the thermal conductivity.

[0322] (Tensile strength / Elongation rate)

[0323] Each test piece was processed into a No. 10 test piece of Japanese JIS Z 2241, and the tensile strength and elongation rate were measured.

[0324] For hot-extruded or hot-forged parts without cold working process, the tensile strength is preferably 460 N / mm 2 or more, more preferably 490 N / mm 2 or more, further preferably 520 N / mm 2 or more, which is the highest level among free-cutting copper alloys, thus enabling the thin-walling and lightweighting of components used in various fields or the increase of allowable stress. And in the balance between strength and elongation rate, if the tensile strength is set as S (N / mm 2 ), and the elongation rate is set as E (%), then the characteristic relational expression f7 = S × {(E + 100) / 100} 1 / 2 representing the balance between strength and ductility is preferably 540 or more, which is a measure for high-strength and high-ductility materials. f7 is more preferably 570 or more, further preferably 600 or more. It can be said to be a very high level among free-cutting copper alloys. Most of the parts used in faucet fittings, valves, joints, pressure vessels, air conditioners and refrigerators are made of hot-forged or hot-extruded rods. The tensile strength of the currently used Pb-added copper alloy C3604 is about 390 - 420 N / mm 2 and the elongation rate is 30 - 35%, and f7 is about 470. In contrast, in this embodiment, through high-strengthening and due to good dezincification corrosion resistance and stress corrosion cracking resistance, lightweighting can be achieved.

[0325] <Cutting property test using a lathe>

[0326] The evaluation of cutting property was carried out by a cutting test using a lathe in the following manner.

[0327] Cutting processing is performed on hot-extruded bars (processes AA, AB, process B) and hot forgings (process E) to make test pieces with a diameter of 18 mm. A K10 superhard tool (blade) without a chip breaker is installed on a lathe. Using this lathe, under dry conditions, at rake angle: 0°, cutting edge radius: 0.4 mm, clearance angle: 6°, cutting speed: 40 m / min or 110 m / min, cutting depth: 1.0 mm, feed rate: 0.11 mm / rev, cutting is performed on the circumference of the test piece with a diameter of 18 mm. The influence of the cutting speed is also investigated in the embodiments of the present application.

[0328] The signals emitted from a dynamometer composed of three parts (manufactured by MIHODENKI Co., Ltd., AST type tool dynamometer AST-TL1003) installed on the tool are converted into electrical voltage signals and recorded on a recorder. Then, these signals are converted into cutting resistance (main component force, feed component force, back component force, N). In the cutting test, in order to suppress the influence of tool wear, A→B→C→……C→B→A is reciprocally performed twice, and each sample is measured four times. The cutting resistance is obtained by the following formula.

[0329] Cutting resistance (resultant force of main component force, feed component force, back component force) = ((main component force) 2 +(feed component force) 2 +(back component force) 2 ) 1 / 2

[0330] Here, in the cutting resistance, the main component force is the largest, and the cutting resistance is roughly determined by the magnitude of the main component force. Therefore, the main component force is used as the cutting resistance, and the average value of the four measured values is calculated as the cutting resistance.

[0331] Taking the cutting resistance (main component force) of a commercially available free-cutting brass bar C3604 (alloy X, φ20 mm) composed of an alloy of Zn - 59 mass% Cu - 3 mass% Pb - 0.2 mass% Fe - 0.3 mass% Sn as 100, the relative value (cutting performance index) of the cutting resistance of the sample is calculated for relative evaluation. That is, the higher the cutting performance index, the lower the cutting resistance, and thus the better the cutting performance.

[0332] In addition, the cutting performance index is obtained in the following manner.

[0333] Index of the cutting test result of the sample (cutting performance index) = (cutting resistance (main component force) of C3604 / cutting resistance (main component force) of the sample) × 100

[0334] The cutting resistance (main component) depends on the shear strength and tensile strength of the material, and there is a tendency that the higher the material strength, the higher the cutting resistance. For example, when a copper alloy has the same good chip breakability as C3604 but its strength is about 1.2 times that of C3604, since the cutting resistance is proportional to the material strength, the cutting resistance is approximately 20% higher than that of C3604. Therefore, when it comes to a copper alloy with high strength, if the cutting resistance is about 40% higher than that of C3604, it is considered to have good practicality. In this embodiment, the tensile strength and shear strength of the extruded part are approximately 1.2 times that of C3604. Therefore, regarding the evaluation criterion for the machinability in this embodiment, it is evaluated with a cutting property index of about 72 as the boundary (threshold value). Specifically, if the cutting property index is 80 or more, it is evaluated as excellent machinability (evaluation: A, excellent), and it has the same machinability as C3604. If the cutting property index is 72 or more and less than 80, it is evaluated as good machinability (evaluation: B, good). If the cutting property index is 66 or more and less than 72, it is evaluated as acceptable machinability (evaluation: C, qualified). If the cutting property index is less than 66, it is evaluated as poor machinability (evaluation: D, unqualified). In this application, the goal is good machinability, so a cutting property index of 72 or more is regarded as qualified.

[0335] (dezincification corrosion test: ISO 6509 dezincification corrosion test)

[0336] As a dezincification corrosion test method, it is evaluated using the ISO 6509 dezincification corrosion test. This test method has been adopted by many countries and is also specified in Japanese JIS H 3250 in the Japanese JIS standards.

[0337] The procedure of the dezincification corrosion test is as follows: First, embed the test piece into a phenolic resin piece. Specifically, embed it into the phenolic resin piece in such a way that the exposed surface of the test sample is perpendicular to the extrusion direction of the extruded part. Grind the surface of the test sample with sandpaper before 1200 grit, and then perform ultrasonic cleaning in pure water and dry it.

[0338] Immerse each test sample in an aqueous solution (12.7 g / L) of 1.0% copper(II) chloride dihydrate (CuCl 2 ·2H 2 O) and keep it at a temperature of 75 °C for 24 hours. Then, take out the test sample from the aqueous solution.

[0339] Embed the test sample into the phenolic resin piece again in such a way that the exposed surface is perpendicular to the extrusion direction, the length direction, or the forging flow direction. Then, cut the test sample to obtain a cut part with the longest cross-section of the corroded part. Next, grind the test sample.

[0340] Using a metallurgical microscope, observe the corrosion depth at ten positions in the microscope field of view at a magnification of 100 - 500 times. Record the deepest corrosion point as the maximum dezincification corrosion depth.

[0341] In addition, when conducting the test of ISO 6509, if the maximum corrosion depth is 200 μm or less, it is regarded as a level with no problem in corrosion resistance during actual use. When excellent corrosion resistance is required, the maximum corrosion depth is preferably 100 μm or less.

[0342] In this test, the case where the maximum corrosion depth exceeds 200 μm is evaluated as poor (evaluation: D, unqualified). The case where the maximum corrosion depth exceeds 100 μm and is 200 μm or less is evaluated as good (evaluation: B, good). The case where the maximum corrosion depth is 100 μm or less is evaluated as excellent (evaluation: A, excellent).

[0343] (Stress corrosion cracking test)

[0344] In order to judge whether it can withstand the stress corrosion cracking environment, conduct the stress corrosion cracking test in the following order.

[0345] First, cut a φ20 mm rod to a weight of 120 ± 1 g (119 - 121 g) as the test specimen, and under the conditions of process D in Table 14, use a 500 - ton hot forging press to form it into a flared nut forging blank with a 27 - mm across - flats and a 26 - mm length of a hexagon. Further, as shown in Table 14, perform shot peening on some test materials in the same way as process No. D7, and as shown in Table 17, perform heat treatment on the forging blanks under various conditions (process No. G2, G3, G12H, G14H). Perform thread cutting on these forging blanks by machining, and finish - machine the end faces, etc., to finish - machine into a kind of flared nut that conforms to Japanese JIS B 8607 and has an inner diameter of 5 / 8 inches ( = 15.9 mm). In order to apply a load stress to the flared nut, prepare a base made of C6932 with an external thread shape that is also machined to conform to Japanese JIS B 8607 and has a nominal diameter of 5 / 8 inches ( = 15.9 mm) for the flared nut joint. Fasten a torque meter to this base until a specific torque is reached. Place a specific concentration of ammonia water in a dryer, place the flared nut under the state of applied load stress at a position 60 mm above the liquid level, keep it for a specific time, and then take out the flared nut. The test is carried out in a room controlled by air - conditioning equipment at 25 ± 1 °C (24 - 26 °C).

[0346] The stress corrosion cracking test is carried out by the following two methods.

[0347] (Stress corrosion cracking test - 1)

[0348] Using ammonia water with an ammonia concentration of 14 vol%, 1000 ml of ammonia water was placed in a dryer, and a sample loaded with a torque of 70 N·m was exposed in the dryer for 48 hours and 96 hours. The sample was washed with 10 vol% sulfuric acid and then visually observed and evaluated based on the presence or absence of cracking. Except for the exposure time, this test was carried out using a method conforming to Japanese JIS H 3250. In Japanese JIS H 3250, the exposure time is 2 hours. In contrast, in this method, the exposure time is more than 20 times longer, and the stress corrosion cracking test is more severe. In this application, since the goal is good stress corrosion cracking resistance, the case where cracking is observed after 48 hours of exposure is judged as "D" (unqualified). The case where no cracking is observed after 48 hours of exposure but cracking is observed after 96 hours of exposure is judged as "C" (qualified). The case where no cracking is observed after 96 hours of exposure is judged as "B" (good). In addition, being judged as "C" is acceptable.

[0349] (Stress Corrosion Cracking Test - 2)

[0350] As another stress corrosion cracking test, 200 ml of ammonia water with an ammonia concentration of 28 vol% was placed in a dryer, and a sample loaded with a torque of 150 N·m was exposed in the dryer for 75 hours. The sample was taken out of the dryer, washed with 10 vol% sulfuric acid, and then visually observed for cracking. Compared with the stress corrosion cracking test - 1, the ammonia concentration is higher and the load torque is greater, so the following judgment criteria are adopted. The case where clear visual observation shows that the maximum cracking seen visually is more than 1 / 2 of the length of the sample, i.e., more than 13 mm, is judged as "D" (unqualified). The case where clear visual observation shows that the cracking is more than about 1 / 5 of the length of the sample, i.e., more than 5 mm and less than 13 mm, is judged as "C" (qualified). The case where clear visual observation shows that the cracking is less than about 1 / 5 of the length of the sample, i.e., less than 5 mm (including no cracking), is judged as "B" (good). In addition, being judged as "C" is acceptable.

[0351] [Table 18]

[0352]

[0353] [Table 19]

[0354]

[0355] [Table 20]

[0356]

[0357] [Table 21]

[0358]

[0359] [Table 22]

[0360]

[0361] [Table 23]

[0362]

[0363] [Table 24]

[0364]

[0365] [Table 25]

[0366]

[0367] [Table 26]

[0368]

[0369] [Table 27]

[0370]

[0371] [Table 28]

[0372]

[0373] [Table 29]

[0374]

[0375] [Table 30]

[0376]

[0377] [Table 31]

[0378]

[0379] [Table 32]

[0380]

[0381] [Table 33]

[0382]

[0383] [Table 34]

[0384]

[0385] [Table 35]

[0386]

[0387] [Table 36]

[0388]

[0389] [Table 37]

[0390]

[0391] [Table 38]

[0392]

[0393] [Table 39]

[0394]

[0395] [Table 40]

[0396]

[0397] [Table 41]

[0398]

[0399] [Table 42]

[0400]

[0401] [Table 43]

[0402]

[0403] [Table 44]

[0404]

[0405] [Table 45]

[0406]

[0407] [Table 46]

[0408]

[0409] [Table 47]

[0410]

[0411] [Table 48]

[0412]

[0413] [Table 49]

[0414]

[0415] [Table 50]

[0416]

[0417] [Table 51]

[0418]

[0419] [Table 52]

[0420]

[0421] [Table 53]

[0422]

[0423] [Table 54]

[0424]

[0425] [Table 55]

[0426]

[0427] [Table 56]

[0428]

[0429] 1) It can be confirmed that by satisfying the composition of this embodiment and satisfying the composition relationships f0 to f2, the requirements of the metallographic structure, and the structure and composition relationships f3 to f5, and the structure and composition relationship f6, the following hot-extruded parts and hot-forged parts are obtained: with less Pb content, good machinability can be obtained, good dezincification corrosion resistance and stress corrosion cracking resistance, with a high conductivity of 15% IACS or more, high strength, good ductility, and a high balance between strength and ductility (characteristic relationship f7). Further, the presence of P compounds has the effect of greatly improving machinability, but the β1 phase obtained by modifying the β phase further improves machinability. At the same time, as described below, it can be confirmed that the modification of the β phase greatly improves the main problems of the conventional β phase, namely dezincification corrosion resistance and stress corrosion cracking resistance (alloy Nos. S01, S02, S03, S11, S12, S13, S21 to S46).

[0430] 2) By containing more than 0.50% by mass of Si, the β phase is modified, and grain boundaries are observed within the β1 phase. As a result, good dezincification corrosion resistance and stress corrosion cracking resistance are obtained, and the cutting resistance is reduced (the machinability index increases). When the Si content is 0.65% by mass or more, the dezincification corrosion resistance, stress corrosion cracking resistance, and machinability are further improved. That is, it is considered that the β phase is more modified. On the other hand, if the Si content exceeds 1.20% by mass, the conductivity decreases (alloy Nos. S01, S37, S48, S49, S74, S78, S80, etc.).

[0431] 3) By containing P in an amount exceeding 0.01% by mass, the β-phase is modified, and grain boundaries are observed within the β1-phase. As a result, the dezincification corrosion resistance and stress corrosion cracking resistance are good, and the cutting resistance is reduced. When the P content is 0.03% by mass or more, the dezincification corrosion resistance, stress corrosion cracking resistance, and machinability are further improved. That is, it is considered that the β-phase is more modified. If the P content exceeds 0.18% by mass, the elongation value decreases (Alloys No. S01, S31, S71, S75, etc.).

[0432] 4) By having a Cu content exceeding 60.5% by mass, the β-phase is modified, and grain boundaries are observed within the β1-phase. As a result, the dezincification corrosion resistance and stress corrosion cracking resistance are good, the ductility is improved, and the cutting resistance is reduced. If the Cu content is high, the β-phase decreases, and in some cases, the γ-phase appears, resulting in a decrease in the balance between strength and ductility and poor machinability (Alloys No. S01, S35, S38, S47, S48, S72, S80, Figures 1A to 6A )

[0433] 5) If the Pb content is less than 0.002% by mass, the machinability is poor (Alloy No. S73). If the Pb content is 0.003% by mass or more, further 0.01% by mass or more, the machinability is better (Alloys No. S33, S23). It can be confirmed that if Bi is contained, the cutting resistance equivalent to Pb is reduced (Alloys No. S01, S32, etc.).

[0434] 6) If Sn in an amount exceeding 0.05% by mass is contained, the dezincification corrosion resistance is better. By containing Sn in an amount exceeding 0.10% by mass, the dezincification corrosion resistance is even better. Also, the stress corrosion cracking resistance is improved. On the other hand, if Sn in an amount of 0.90% by mass or more is contained, the γ-phase appears, resulting in a deterioration of the dezincification corrosion resistance, a decrease in ductility, and an increase in cutting resistance (a decrease in the machinability index). Also, if Sn / Si is 1 or more, the β-phase is not modified, and the dezincification corrosion resistance deteriorates (Alloys No. S01, S39 - S46, S82, S83).

[0435] 7) It can be confirmed that even if inevitable impurities in an amount that appears in actual operation are contained, they do not have a significant impact on many properties (Alloys No. S01, S02, S03, S11 - S13, S27 - S30).

[0436] 8) If the total content of inevitable impurities Fe, Mn, Co, and Cr is 0.40 mass% or more, the β-phase is modified, but the cutting resistance is large, the balance between strength and ductility is poor, and the dezincification corrosion resistance is also slightly poor. If the total content of Fe, Mn, Co, and Cr is less than 0.40 mass%, the cutting resistance decreases, the balance between strength and ductility is improved, and the dezincification corrosion resistance and stress corrosion cracking resistance are good. Moreover, if the total content of Fe, Mn, Co, and Cr is less than 0.30 mass%, the cutting resistance further decreases, the balance between strength and ductility is improved, and the dezincification corrosion resistance and stress corrosion cracking resistance are good. It is considered that the decrease in cutting resistance, the balance between strength and ductility, and the decrease in dezincification corrosion resistance are caused by the following reasons. It is considered that Fe, Mn, etc. combine with a part of Si and P to form intermetallic compounds of Fe, Mn, etc. and Si, P. The results show that there are compounds of Fe, etc. and Si, P, and the Si concentration and P concentration that effectively modify the β-phase decrease, resulting in poor machinability and corrosion resistance (alloy Nos. S01, S02, S84, S25 - S30).

[0437] 9) If the amount of inevitable impurity Al is 0.30 mass% or more, the β-phase is not modified and the dezincification corrosion resistance is poor. If the amount of Al is less than 0.30 mass%, the β-phase is modified and the dezincification corrosion resistance is good. Moreover, if the amount of Al is less than 0.15 mass%, the machinability, the balance between strength and ductility, the dezincification corrosion resistance, and the stress corrosion cracking resistance are good (alloy Nos. S01, S85, S26, S28 - S30).

[0438] 10) If the composition relationship formula f1 is small, the β-phase is not modified and the dezincification corrosion resistance is poor. If the composition relationship formula f1 is large, the area ratio of the β1-phase decreases (alloy Nos. S76, S79). If the value of the composition relationship formula f1 is 57.5 or more, the β-phase is modified and the dezincification corrosion resistance is better, and it is even better when the value of the composition relationship formula f1 is 58.0 or more. On the other hand, if the value of the composition relationship formula f1 is 60.5 or less, the area ratio of the β1-phase increases, and it further increases when the value of the composition relationship formula f1 is 60.2 or less, and the machinability index increases (for example, alloy Nos. S01, S03, S35, S36).

[0439] 11) If the area ratio of the β1 phase is 25% or less, good machinability cannot be obtained. If the area ratio of the β1 phase exceeds 25%, and further exceeds 30%, the cutting resistance decreases. If the area ratio of the β1 phase exceeds 80%, the situation where the β phase is not modified increases, that is, no grain boundaries are observed in the β phase, resulting in an increase in cutting resistance, especially the cutting resistance at 110 m / min, and poor dezincification corrosion resistance and stress corrosion cracking resistance. If the area ratio of the β1 phase is 80% or less, and further 70% or less, the β phase is modified, and the dezincification corrosion resistance and stress corrosion cracking resistance are better. In dezincification corrosion, although the progress of dezincification corrosion is significantly delayed by modifying the β phase, the β1 phase is more dezincified than the α phase. Therefore, if the area ratio of the β1 phase is high, the progress of dezincification corrosion is slightly accelerated (alloy No.S03, S11, S72, S81, S76, process D1, D11H, E1, E11H, Figure 1B etc.).

[0440] 12) If the area ratio of the γ phase is 4% or more, the value of elongation decreases. Also, the cutting resistance increases (alloy No.S78, S82).

[0441] 13) If the structure and composition relationship f6 is small, the machinability is poor (alloy No.S81). If f6 exceeds 35, the machinability is better (for example, alloy No.S12, process No.E3, E4, alloy No.S02, process D11H).

[0442] 14) After hot extrusion, if the starting temperature of the cooling treatment exceeds 500 °C and the average cooling rate in the temperature range from the starting temperature of the cooling treatment to 300 °C and the average cooling rate in the temperature range from 500 °C to 300 °C exceed 300 °C / min for cooling, the β phase is modified and grain boundaries are observed in the β1 phase. If the β phase is modified, the cutting resistance decreases, and the dezincification corrosion resistance and stress corrosion cracking resistance are greatly improved, with high strength and an improved balance between strength and ductility. Regarding machinability, when the β phase is modified, even if the cutting speed is increased, the machinability slightly decreases (process No.A1~A5, D1~D5, E1~E5, F1~F3, G1~G3, Figures 1A to 6A etc.).

[0443] 15) When the starting temperature of the cooling treatment exceeds 500 °C and is lower than about 530 °C, and when the average cooling rate in the temperature range from 500 °C to 300 °C is about 400~about 500 °C / min, sometimes grain boundaries are also observed in the β1 phase and a small amount of P compound exists. When a small amount of P compound exists, compared with the case where no P compound exists, the cutting resistance slightly increases and the dezincification corrosion resistance is slightly poor (process No.A1~A5, D1~D5, E1~E5, F1~F3, G1~G3,Figures 1A to 6A , Figures 1B to 6B , etc.)

[0444] 16) When the average cooling rate in the temperature range of 500 °C to 300 °C is about 200 - 250 °C / min, no grain boundaries are observed in the β1 phase, and there are often a small amount of P compounds. The result that no grain boundaries are observed in the β1 phase indicates that the machinability, especially the machinability at 110 m / min, is poor, and the dezincification corrosion resistance is poor (Process No. A14H, D14H, etc.).

[0445] 17) If the cooling treatment start temperature is 550 °C or higher, and the average cooling rate in the temperature range from the cooling treatment start temperature to 300 °C and the average cooling rate in the temperature range of 500 °C to 300 °C are the preferred cooling rates, the machinability index increases, and the dezincification corrosion resistance and stress corrosion cracking resistance are good. That is, it is considered that if the cooling treatment starts at an appropriate temperature and the cooling rate is fast, the β phase is further modified (Process No. A1 - A5, A11H - A14H, D1 - D5, D11H - D14H, E1 - E5, E11H - E15H, F1 - F3, F4H, F5H, G1 - G3, G11H - G14H, Figures 1B to 6B , etc.)

[0446] 18) When the start temperature of the cooling treatment is higher than 670 °C, the proportion of the β1 phase increases, the cutting resistance is slightly larger, especially the cutting resistance at 110 m / min is large, and the dezincification corrosion resistance is slightly poor. If the proportion of the β1 phase is too large, sometimes the β phase will not be modified. In addition, the form of dezincification corrosion is the selective corrosion of the β1 phase. If the proportion of the β1 phase is large, the progress rate of dezincification corrosion is also slightly faster (Process No. A1 - A5, D1 - D5, E1 - E5, F1 - F3, G1 - G3, etc.).

[0447] 19) If the β phase is modified and the β1 phase is observed, the stress corrosion cracking resistance is good, and all are judged as "B" in the stress corrosion cracking test - 1 (Process No. D1 - D5).

[0448] 20) By performing shot peening after hot working (hot forging), the stress corrosion cracking resistance is better, and all are judged as "B" in the stress corrosion cracking test - 1 and the stress corrosion cracking test - 2. On the other hand, for the specimens where the β1 phase is not observed or the Si content is low, shot peening does not improve the stress corrosion cracking resistance (Process No. D3, D7, Alloy No. S71, 80).

[0449] 21) It can be confirmed that when there are two hot working processes, for example, when hot forging a bar after extrusion in the hot state, regardless of the cooling method after the initial hot working, as long as the cooling treatment of the final hot working, i.e., hot forging, is appropriate, the β phase is modified (Process Nos. D1 to D5, D7).

[0450] 22) It can be confirmed that even if the blank for hot forging is a casting, as long as the cooling treatment after hot forging is appropriate, similar to the hot extruded parts, the β1 phase can be observed and the same properties can be obtained (Process Nos. D6, E6, F1).

[0451] 23) If the alloy with the modified β phase is held at 300 °C for 2 hours, the grain boundaries of the β1 phase disappear. As a result, the machinability deteriorates and the dezincification corrosion resistance also deteriorates. Under the conditions of 130 °C and 5 hours, the grain boundaries of the β1 phase are observed and no decrease in machinability and dezincification corrosion resistance is seen (Process Nos. A21, A25, A31H).

[0452] 24) It can be confirmed that even if no specific cooling treatment is implemented in the final hot working, by annealing the hot worked parts under the condition of holding at a temperature exceeding 520 °C and lower than 630 °C for 1 minute to 5 hours, after annealing, starting the cooling treatment at a temperature higher than 500 °C and cooling in such a way that the average cooling rate in the temperature range from the cooling treatment start temperature to 500 °C and the average cooling rate in the temperature range from 500 °C to 300 °C exceed 300 °C / minute, the β phase is also modified. In particular, the dezincification corrosion resistance and stress corrosion cracking resistance are greatly improved (Process Nos. G1 to G3, Figure 5A , Figure 5B ).

[0453] Based on the above, for the alloy of the present embodiment, such as the alloy of the present embodiment, the hot workability of the alloy of the present embodiment in which the content and composition relationship of each additive element and each tissue relationship are within an appropriate range is excellent, and the machinability, mechanical properties, dezincification corrosion resistance, and stress corrosion cracking resistance are good. Moreover, excellent properties of the alloy of the present embodiment can be obtained by setting the manufacturing conditions in hot extrusion and hot forging and the conditions in heat treatment to an appropriate range.

[0454] Industrial Applicability

[0455] The free-cutting copper alloy of the present embodiment has a small Pb content, excellent hot workability and machinability, high strength, and excellent balance between strength and elongation. Therefore, the free-cutting copper alloy of the present embodiment is suitable for appliances and parts related to drinking water and sanitary equipment, food appliances, electrical and electronic equipment parts, automotive parts, mechanical parts, stationery, toys, musical instruments, sliding parts, measuring instrument parts, precision mechanical parts, medical parts, beverage appliances and parts, water meters, and parts related to liquids or gases such as industrial water, drainage, and hydrogen.

[0456] Specifically, it can be suitably used as a constituent member of parts named as faucet, stop faucet, mixing faucet, shower head, valve, joint, cock, gear, shaft, bearing, bellows, rotating shaft, sleeve, mandrel, sensor, bolt, nut, flared nut, pen tip, inserted nut, cap nut, threaded joint, gasket, screw, etc. used in the aforementioned fields.

Claims

1. A free-cutting copper alloy, characterized in that: Contains more than 60.5 mass % and less than 65.0 mass % of Cu, more than 0.50 mass % and less than 1.20 mass % of Si, 0.002 mass % or more and less than 0.20 mass % of Pb, and more than 0.01 mass % and less than 0.18 mass % of P, and contains 0.0001 mass % or more and less than 0.20 mass % of Bi as an optional element, with the remainder being Zn and unavoidable impurities, Among the unavoidable impurities, the total content of Fe, Mn, Co and Cr is less than 0.40 mass %, and the content of Al is less than 0.30 mass %. When the content of Cu is [Cu] mass%, the content of Si is [Si] mass%, the content of Pb is [Pb] mass%, the content of P is [P] mass%, and the content of Bi is [Bi] mass%, the following relationship is held: 57.5≤f1=[Cu]-4.6×[Si]+0.5×([Pb]+[Bi])-[P]≤60.5, When Bi is included, the following relationship is further satisfied: 0.003≤f2=[Pb]+[Bi]<0.20, And when the area ratio of the α phase is set to α%, the area ratio of the γ phase is set to γ%, and the area ratio of the β1 phase as the modified β phase is set to β1% in the constituent phases of the metallographic structure excluding non-metallic inclusions, the following relationship is held: 20≤f3=α<75、 25<f4=β1≤80、 0≤f5=γ<4、 27<f6=β1×([Si]) 1 / 2 -γ×2+([Pb]+[Bi]) 1 / 2 ×20+([P]) 1 / 2 ×15, When the β1 phase is etched with a mixed solution of hydrogen peroxide and ammonia water, grain boundaries are observed.

2. A free-cutting copper alloy, characterized in that: Contains 61.2 mass % or more and 64.8 mass % or less of Cu, 0.65 mass % or more and 1.10 mass % or less of Si, 0.003 mass % or more and less than 0.10 mass % of Pb, and 0.03 mass % or more and less than 0.15 mass % of P, and contains 0.001 mass % or more and less than 0.10 mass % of Bi as an optional element, and the remainder is Zn and unavoidable impurities, Among the unavoidable impurities, the total content of Fe, Mn, Co and Cr is less than 0.30 mass %, and the content of Al is less than 0.15 mass %. When the content of Cu is [Cu] mass%, the content of Si is [Si] mass%, the content of Pb is [Pb] mass%, the content of P is [P] mass%, and the content of Bi is [Bi] mass%, the following relationship is held: 58.0≤f1=[Cu]-4.6×[Si]+0.5×([Pb]+[Bi])-[P]≤60.2, When Bi is included, the following relationship is further satisfied: 0.004≤f2=[Pb]+[Bi]<0.10, And when the area ratio of the α phase is set to α%, the area ratio of the γ phase is set to γ%, and the area ratio of the β1 phase as the modified β phase is set to β1% in the constituent phases of the metallographic structure excluding non-metallic inclusions, the following relationship is held: 30≤f3=α≤70、 30≤f4=β1≤70、 0≤f5=γ<1, 35<f6=β1×([Si]) 1 / 2 -γ×2+([Pb]+[Bi]) 1 / 2 ×20+([P]) 1 / 2 ×15, When the β1 phase is etched with a mixed solution of hydrogen peroxide and ammonia water, grain boundaries are observed.

3. A free-cutting copper alloy, characterized in that: The invention comprises more than 60.5 mass % and less than 65.0 mass % of Cu, more than 0.50 mass % and less than 1.20 mass % of Si, 0.002 mass % and less than 0.20 mass % of Pb, more than 0.01 mass % and less than 0.18 mass % of P, and more than 0.05 mass % and less than 0.90 mass % of Sn, and contains 0.0001 mass % and less than 0.20 mass % of Bi as an optional element, with the remainder being Zn and unavoidable impurities, Among the unavoidable impurities, the total content of Fe, Mn, Co and Cr is less than 0.40 mass %, and the content of Al is less than 0.30 mass %. When the content of Cu is [Cu] mass%, the content of Si is [Si] mass%, the content of Pb is [Pb] mass%, the content of P is [P] mass%, the content of Bi is [Bi] mass%, and the content of Sn is [Sn] mass%, the following relationship is held: 57.5≤f1=[Cu]-4.6×[Si]+0.5×([Pb]+[Bi])-[P]-[Sn]≤60.5, and further have the following relationship: f0=[Sn] / [Si]<1, When Bi is included, the following relationship exists: 0.003≤f2=[Pb]+[Bi]<0.20, And when the area ratio of the α phase is set to α%, the area ratio of the γ phase is set to γ%, and the area ratio of the β1 phase as the modified β phase is set to β1% in the constituent phases of the metallographic structure excluding non-metallic inclusions, the following relationship is held: 20≤f3=α<75、 25<f4=β1≤80、 0≤f5=γ<4、 27<f6=β1×([Si]) 1 / 2 -γ×2+([Pb]+[Bi]) 1 / 2 ×20+([P]) 1 / 2 ×15, Regarding the β1 phase, when etching is performed using a mixed solution of hydrogen peroxide and ammonia water, grain boundaries are observed.

4. A free-cutting copper alloy, characterized in that: The invention comprises 61.2 mass % to 64.8 mass % of Cu, 0.65 mass % to 1.10 mass % of Si, 0.003 mass % to less than 0.10 mass % of Pb, 0.03 mass % to 0.15 mass % of P, 0.10 mass % to less than 0.50 mass % of Sn, 0.001 mass % to less than 0.10 mass % of Bi as an optional element, and the remainder is Zn and unavoidable impurities, Among the unavoidable impurities, the total content of Fe, Mn, Co and Cr is less than 0.30 mass %, and the content of Al is less than 0.15 mass %. When the content of Cu is [Cu] mass%, the content of Si is [Si] mass%, the content of Pb is [Pb] mass%, the content of P is [P] mass%, the content of Bi is [Bi] mass%, and the content of Sn is [Sn] mass%, the following relationship is held: 58.0≤f1=[Cu]-4.6×[Si]+0.5×([Pb]+[Bi])-[P]-[Sn]≤60.2, and further have the following relationship: f0=[Sn] / [Si]<0.6, When Bi is included, the following relationship exists: 0.004≤f2=[Pb]+[Bi]<0.10, And when the area ratio of the α phase is set to α%, the area ratio of the γ phase is set to γ%, and the area ratio of the β1 phase as the modified β phase is set to β1% in the constituent phases of the metallographic structure excluding non-metallic inclusions, the following relationship is held: 30≤f3=α≤70、 30≤f4=β1≤70、 0≤f5=γ<1, 35<f6=β1×([Si]) 1 / 2 -γ×2+([Pb]+[Bi]) 1 / 2 ×20+([P]) 1 / 2 ×15, When the β1 phase is etched with a mixed solution of hydrogen peroxide and ammonia water, grain boundaries are observed.

5. The free-cutting copper alloy according to any one of claims 1 to 4, characterized in that: The free-cutting copper alloy is used for appliances and parts related to drinking water and sanitary equipment, valves, cocks, industrial pipe parts, water meters, musical instruments, automobile parts, electrical and electronic equipment parts, mechanical parts, stationery, toys, sliding parts, measuring instrument parts, precision machinery parts and medical parts.

6. A method for producing a free-cutting copper alloy, characterized in that: The manufacturing method manufactures the free-cutting copper alloy according to any one of claims 1 to 4, Having more than one thermal processing step, In the final hot working step in the hot working step, the hot working temperature exceeds 540°C and is less than 750°C. In the cooling process after the hot working, the hot-worked part is cooled at a temperature lower than 670°C and higher than 500°C. During the cooling process, the hot-worked part is cooled in a manner such that the average cooling rate in the temperature range from the cooling starting temperature to 500°C exceeds 300°C / minute and the average cooling rate in the temperature range from 500°C to 300°C exceeds 300°C / minute.

7. A method for producing a free-cutting copper alloy, characterized in that: The manufacturing method manufactures the free-cutting copper alloy according to any one of claims 1 to 4, The invention has one or more hot working steps and heat treatment steps. In the final heat treatment step, annealing is performed under the condition of maintaining a temperature of more than 520°C and less than 630°C for 1 minute to 5 hours. After annealing, cooling treatment is started at a temperature higher than 500°C, and cooling is performed in a manner such that the average cooling rate in the temperature range from the cooling treatment start temperature to 500°C exceeds 300°C / minute and the average cooling rate in the temperature range from 500°C to 300°C exceeds 300°C / minute.

Citation Information

Patent Citations

  • Lead-free free cutting brass excellent in dezincification corrosion resistance and its production method

    JP2002003967A

  • Lead-free free-cutting silicon brass alloy

    JP2010133006A

  • LOW Pb BRASS BAR MATERIAL AND METHOD FOR PRODUCING THE SAME

    JP2016194123A

  • Brass excellent in corrosion resistance

    JP2018048398A

  • Lead-free, free-cutting brass alloy with excellent castability, its manufacturing method, and its uses

    JP2019508584A